Regulating the d-band center of Ru/CoMoO4 ternary heterostructure by interface engineering for accelerated hydrogen adsorption kinetics - Miao Ma; Min Yang; Cai-Yue Zhang; Hai-Yi Sun; Rong-Jing Su; Xiao-Rui Yue; Chen-Xi Li; Yong-Ming Chai; Bin Dong (Fuel, 2026)

Evaluating ecological and socio-economic system dimensions to improve fisheries management in the Bohai Sea, China - Jie Yin; Jia Wo; Yunzhou Li; Ming Sun; Jacob G. Eurich; Kristin M. Kleisner; Shems B. Jud; Yi Tang; Shu Su; Yaping Ao; Yong Chen (Reviews in Fish Biology and Fisheries, 2026)

Higher mitochondrial DNA methylation is associated with increased risk of stroke: a nested case-control study - Xueru Fu; Yuewan Fang; Yujie Zhao; Bin Yang; Yaqin Su; Li Yang; Weifeng Huo; Liuding Wen; Yuying Wu; Yang Zhao; Fulan Hu; Ming Zhang; et al. (Human Genetics, 2026)

Controlling filamentous cyanobacterial blooms requires adaptive, weather-informed strategy - Jiao Fang; Ming Su; Yande Li; Yuying Gui; Yufan Ai; Ogalo Joseph; Tengxin Cao; Shilong He; Min Yang (Water Research, 2026)

Fracture-controlled reactive transport and fractal permeability evolution during CO₂ + O₂ in situ leaching of uranium-bearing sandstone - Tong Zhang; Bingzhang Li; Xin Yang; Ming Tang; Junlin Mao; Xuebin Su; Liang Yuan (Hydrometallurgy, 2026)

Benzimidazole functionalization enables efficient multi-resonance TADF with accelerated spin-flipping and balanced charge transport - Ji-Hua Tan; Si-Wei Chen; Xin-Lu Li; Han-Nan Shi; Xiao-Long Liu; Yao-Zu Su; Xiaofeng Wang; Jun-Hua Zhuang; Chengxiang Shi; Jia-Ming Jin; Shaoyun Yin; Jia-Xiong Chen; et al. (Chemical Engineering Journal, 2026)

Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

Borborobacter xinjiangensis sp. nov., a moderately halophilic bacterium isolated from grapevine rootstock in Xinjiang, China - Xue Li; Yu Tao; Ming Li; Qingzhuang Zhang; Guohong Wu; Jinge Hu; Shijian Bai; Lei Su; Xin Li (Archives of Microbiology, 2026)

Pore damage evolution and permeability degradation of sandstone-type uranium ore during in-situ leaching: An innovative online true-triaxial LF-NMR experiment - Xin Yang; Tong Zhang; Mingchao Wang; Xuebin Su; Junlin Mao; Bingzhang Li; Shunyu Yao; Qilong Wang; Yongqiang Zhao; Xiaodong Nie; Ming Tang; Boshan Duan (Hydrometallurgy, 2026)

Effects of carriers and addition modes on the physical and chemical properties of green pepper (Piper nigrum L.) powders treated by freeze-far infrared drying during storage - Xinyi Wang; Yiling Tang; Yue Huang; Hui Su; Xiaoyu Fan; Hongchen Li; Haiming Chen; Ming Zhang; Jianfei Pei; Congfa Li; Wenxue Chen; Ying Lyu (Food Chemistry, 2026)

Development of TM hypoallergenic enzymatic products with the potential to induce immune tolerance in Lateolabrax japonicus - Meng-Si Li; Qing-Mei Liu; Fei Xia; Su-Jie Huang; Shun-Xian Lin; Li-Qiang Zhong; Hao-Tian Zhang; Gui-Xia Chen; Guang-Ming Liu (Food Bioscience, 2026)

Corrigendum to “Multiple environmental drivers shape zooplankton community structure in a subtropical-tropical transitional coastal system” [Estuar. Coast Shelf Sci. 340 (2026) 110113] - Zhao-Lang Huang; Shuang Liu; Yan-Guo Wang; Pu-Qing Song; Rou-Xin Sun; Bing-Peng Xing; Su-Min Wang; Jian-Hua Kang; Geng-Ming Lin; Ping Li (Estuarine, Coastal and Shelf Science, 2026)

Multiple environmental drivers shape zooplankton community structure in a subtropical-tropical transitional coastal system - Zhao-Lang Huang; Shuang Liu; Yan-Guo Wang; Pu-Qing Song; Rou-Xin Sun; Bing-Peng Xing; Su-Min Wang; Jian-Hua Kang; Geng-Ming Lin; Ping Li (Estuarine, Coastal and Shelf Science, 2026)

Low-cost pillar-ligand engineering toward ultramicroporous MOFs for efficient SF6/N2 separation - Biao Fu; Hui-Ting Zheng; Rui-Ming Li; Duo Yue; Liang Song; Zhang-Wen Wei; Robert Langer; Mihail Barboiu; Ji-Jun Jiang; Cheng-Yong Su (Chemical Engineering Journal, 2026)

Kosakonia oryziphila KC516 mediated growth promotion of Cosmos bipinnatus in phosphogypsum by modulating rhizosphere geochemistry and root transcriptome - Jing Zhang; Hao-Tian Dong; Yuan-Chun Yang; Rui Liu; Shuai Wang; Ao-Li Zhang; Yuan Su; Ming-Hua Dong; Yan-Ru Cao; Hua-Li Zhang (Environmental Geochemistry and Health, 2026)

Potential microbial mechanism of aerobic methanotrophs combined with nitrate and iron reduction under anaerobic conditions - Xujia Ming; Xudong Wang; Jiaqi Su; Qingfen Liu; Hanghang Song; Xiao Han; Rongguo Su; Xianguo Li; Dahai Zhang (Marine Pollution Bulletin, 2026)

Optimized retrievals of aerosol optical properties from directional polarimetric camera using optimal linear mixture of basis aerosol models supported by the non-negative matrix factorization - Shikuan Jin; Yingying Ma; Deren Li; Wei Gong; Oleg Dubovik; Jin Hong; Zhenghai Liu; Cheng Chen; Zhongting Wang; Tao He; Yunduan Li; Boming Liu; et al. (Remote Sensing of Environment, 2026)

Quaternary submarine slope gullies on the northern South China Sea margin: Architecture, initiation, and evolution - Zhina Wang; Haiteng Zhuo; Zhen Sun; Zhenyu Zhu; Xiujuan Wang; Ming Su; Jie Li; Qi Fan; Shan Liu; Zhixuan Lin (Marine Geology, 2026)

Characterized Prunus cerasifera-derived polyphenols attenuate ALD through regulation of the gut microbiota-SCFAs-TLR4/NF-κB/PTGS2/TNF axis - Jiabao Ren; Linkai Wang; Xiaoying Zhu; Ming Gao; SU Heiyan Perhat; Chunlin Hao; Enpeng He; Yanhong Li (Food Bioscience, 2026)

Ontogenetic shifts in salinity tolerance and metabolic strategies of Heliocidaris crassispina: implications for aquaculture management - Zirui Li; Qiyang Sun; Dejian Su; Yang Ming; Junyi Wen; Zonghe Yu (Aquaculture International, 2026)

Transcriptomic analysis suggests ferroptosis as a potential mechanism of fipronil-induced cytotoxicity in human glioblastoma cells - Yu-Chia Chen; Yu-He Li; Po-Ming Chen; Hsin-Hung Chen; Mei-Tzu Su (Toxicology in Vitro, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Deciphering Qu-aroma in Nongxiangxing baijiu via a customized aroma base solution - Sheng-Bing Yang; Zhen-Ming Lu; Jia-Nan Hu; Ting-Yao Tu; Man-Si Niu; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Jin-Song Shi; et al. (Food Research International, 2026)

A heterotrophic nitrification and aerobic denitrification strain capable of antibiotic degradation: From function to mechanism - Jia-Ying Li; You-Wei Cui; Yuan Sui; Ji-Tao Yan; Xin-Yu Gu; Rui-Chun Yang; Ming-Xin Su; Ze-You Lu (Environmental Pollution, 2026)

Analysis of Arbuscular Mycorrhizal Fungal Community in Soil of Sugarcane at Different Tillage Depths - Qun-Qing Huang; Sheng Wang; Ying-Jie Nong; Kai-Mao Zhong; Yi-Cheng Su; Xiao-Juan Qin; Jin-Lian Zhang; Yi-Hao Kang; Ting-Su Chen; Shi-Yuan Zeng; Xi-Chao Deng; Ming-Guo Jiang; et al. (Sugar Tech, 2026)

Enhancing landslide susceptibility assessment through ensemble learning and PCoA - Ming Chang; Boju Zhao; Yongchao Su; Ning Li; Daolong Yin; Xianxi Zhou; Liang Chen (Bulletin of Engineering Geology and the Environment, 2026)

High-performance quantum interconnect between bosonic modules beyond transmission loss constraints - Hongwei Huang; Jie Zhou; Weizhou Cai; Weiting Wang; Yilong Zhou; Yunlai Zhu; Ziyue Hua; Yifang Xu; Lida Sun; Juan Song; Tang Su; Ming Li; et al. (Science Bulletin, 2026)

Selective catalytic oxidation of ammonia by efficient FeOx in coal ash: insights from experimental and DFT studies - Yili Zhang; Su Zhang; Binxin Fang; Liming Cui; Yixiang Zhang; Wenzhen Zhang; Houzhang Tan; Ming Li; Xuebin Wang (Fuel, 2026)

One-pot biocatalytic synthesis of structurally uniform β-1,3-glucan from renewable cellobiose via a thermostable GH161 phosphorylase in an in vitro biosystem - Guotao Mao; Junhan Lin; Zhe Li; Jin Yu; Ming Song; Miaoqian Wang; Hongsen Zhang; Hui Xie; Zengping Su; Hongge Chen; Andong Song (Food Chemistry, 2026)

Maternal inulin intervention ameliorates lipid metabolism disorders in offspring induced by a high-fat diet before or during pregnancy via the gut-liver-adipose axis - Bing Chen; Jia Wu; Xiaole Cui; Yaxing Miao; Lingling Li; Kaixin Su; Changchun Liu; Yane Luo; Ming Du; Wei Song (Food Bioscience, 2026)

Computational-guided semi-rational design to reprogram phospholipase D into industrially robust enzyme - Xiao-Li Kong; Peng Zhang; Zheng-Qiang Qin; Chang Su; Heng Li; Zhen-Ming Lu; Jin-Song Gong; Zheng-Hong Xu; Jin-Song Shi (Bioresource Technology, 2026)

Gastrodin Ameliorates Blood Pressure by Targeting the PPAR-γ/NF-κB/NLRP3 Signaling Axis in the Hypothalamic Paraventricular Nucleus - Yu Yang; Xiao-Jing Yu; Li-Yan Fu; Jie Qi; Kai-Li Liu; Xiu-Yue Jia; Wei Cui; Qing Su; Ting Huang; Yan-Feng Liang; Hua Tian; Huan Liu; et al. (Cardiovascular Toxicology, 2026)

First report of scale drop disease virus (SDDV) infection in cultured silver pomfret (Pampus argenteus) in China: Isolation and pathogenic characterization - Su-Ming Zhou; Yang-Yang Bai; Deng-Feng Li; Jia-Song Xie; Ya-Jun Wang; Fei Yin (Aquaculture, 2026)

Spatiotemporal decoupling of littoral and lacustrine geosmin dynamics: Implications for early warning in drinking water reservoirs - Yuying Gui; Tengxin Cao; Jie Yang; Jihui Qin; Ming Su; Ziyi Yang; Qi Zhang; Yufan Ai; Jiao Fang; Yingjie Li; Yuanhong Xiao; Zhixiang Hao; et al. (Water Research, 2026)

TomOmics: An integrative multi-omics platform for comparative and functional research in tomato - Yan Wang; Tailai Yang; Yuru Song; Qinqin Yang; Xiao Su; Hongwei Li; Yushan Li; Ming Zhou; Tao Lin (Molecular Plant, 2026)

Experimental study of the spray-wall interaction under wall boiling conditions at both macroscopic and microscopic scales - Yuhe Su; Yanzhi Zhang; Ming Jia; Xinyi Li (Fuel, 2026)

Salinity decrease leads to recovery of filamentous bacterial bulking in moderately halophilic aerobic granules: Unraveling the role of fungi - Ze-You Lu; You-Wei Cui; Ya-Nan Mi; Xin-Yu Gu; Rui-Chun Yang; Ming-Xin Su; Jia-Ying Li (Bioresource Technology, 2026)

Research progress on the application of seaweed extracts in fertilizer synergism - Shaochong Li; Haofeng He; Jingyan Chen; Xinyu Guo; Qiang Li; Ming Lu; Hang Su; Fuli Li (Algal Research, 2026)

Thermal treatment-regulated decomposition and phase transformation of soda residue: product construction and mechanism of simultaneous removal of Cd2+ and Pb2+ from wastewater - Yonglan Zong; Xiaoyi Li; Chenglei Hu; Youbo Su; Ming Jiang (Waste Management, 2026)

Reduction of As(V)-bearing goethite by dissolved organic matter from arsenic-prone groundwater during the repeated electron shuttling - Xiaojun Feng; Zhengqi Su; Simeng Li; Xiaoxing Ming; Di Zhang; Huaming Guo (Journal of Hazardous Materials, 2026)

Experimental study on dual-heat-source collaborative optimization of vehicle CO2 thermal management system using integrated multi-strategy closed-loop algorithm - Haixu Teng; Ming Li; Yulong Li; Han Su; Shuangyuan Xiong; Chunhong Lu; Xinyue Feng; Yan Jiang (International Journal of Refrigeration, 2026)

Biocatalytic potential of salt-stress domesticated Aspergillus strains in mackerel offal fermentation: A high-throughput sequencing-guided analysis of fish sauce microbiota - Jing Li; Jiabo Huang; Shuhong Ye; Wentao Su; Ming Du; Pengfei Jiang (Food Bioscience, 2026)

Luteolin exhibits broad-spectrum antiviral activity against swine enteric coronaviruses by targeting 3CLpro - Xiaoxu Xing; Jiongze Cheng; Huinan Li; Ming Liu; Minghui Gu; Jiawei Xiao; Hansong Li; Lan Bi; Feiyu Zhao; Haixin Liu; Donghua Guo; Mingjun Su; et al. (Veterinary Microbiology, 2026)

Driving factors on bacterial community of heterotrophic nitrification and aerobic denitrification in real wastewater treatment plants: Evidence from different latitudinal gradients in warm season - Rui-Chun Yang; You-Wei Cui; Zhen-Ying Li; Yuan Sui; Tong Ren; Xin-Yu Gu; Ming-Xin Su; Ze-You Lu (Journal of Water Process Engineering, 2026)

Who is the best allogeneic hematopoietic stem cell transplant donor for severe aplastic anemia? Data from the Chinese Bone Marrow Transplantation Registry Group (CBMTRG) - Zheng-Li Xu; Lan-Ping Xu; Shun-Qing Wang; De-Pei Wu; Xi Zhang; Su-Jun Gao; Ling-Hui Xia; Rui Xi; Jian-Min Yang; Qi-Fa Liu; Ming Jiang; Xiao-Sheng Fang; et al. (Science Bulletin, 2026)

Static magnetic field coupled with control of sludge retention time enhancing nitrogen removal via heterotrophic nitrification-aerobic denitrification - Ming-Xin Su; You-Wei Cui; Rui-Chun Yang; Yuan Sui; Xin-Yu Gu; Jia-Ying Li; Ze-You Lu (Journal of Water Process Engineering, 2026)

Efficient stacking ensemble machine learning for 1 km daily PM2.5 and PM10 mapping in Beijing-Tianjin-Hebei - Yumeng Li; Xin Su; Lunche Wang; Lan Feng; Xiaoyu Ma; Ming Zhang; Shikuan Jin (Atmospheric Environment, 2026)

Allelopathic effects of native plant litter extracts on seedling establishment of the invasive plants Bidens Alba and Mikania Micrantha - Yu-Qi Fang; Zhe-Yang Su; Chong-Wei Li; Bao-Ming Chen (Plant Ecology, 2026)

Decontamination of volatile compounds from post-consumer recycled HDPE via supercritical CO2: Unravelling the critical role of co-solvent molecular structure - Ming-Yue Zhang; Qi-Zhi Su; Can Xu; Tian-Long Zhang; Huai-Ning Zhong; Qin-Bao Lin; Dan Li; Ben Dong (Waste Management, 2026)

An unprecedented alternariol-zinnol hybrid and six undescribed zinnol derivatives from the phytopathogen Alternaria solani and their cytotoxic activities - Ming Hu; Run-Cheng Yan; Qiao-Ling Wei; Jiang-Li Su; Bi-Juan Yang; Wen-Chao Tu; Gan-Peng Li; Xing-De Wu (Phytochemistry, 2026)

Human activities and horizontal gene transfer shape the resistome landscapes of non-human primates - Yue Sun; Mingyi Zhang; Yang Teng; Yueqi Yin; Jingcheng Ran; Haijun Su; Hongjia Li; Xiaolong Huang; Zexu Long; Xue Sun; Huijuan Pan; Xiaochen Wang; et al. (Journal of Hazardous Materials, 2026)

Imidazolyl ionic liquid-based hypercrosslinked polymers as adsorbents for reversible capture of iodine - Xiaomeng Su; Ming Zhao; Liqiu Sun; Yue Yu; Jianjun Wang; Liyan Wang; Jun Li; Dan Wang; Liying Qi; Kuo Zhang; Zhichun Shi (Journal of Environmental Chemical Engineering, 2026)

Alkalinity change induces succession of heterotrophic and autotrophic nitrifying bacterial communities: Comprehensive insights on the mechanism - Yuan Sui; You-Wei Cui; Rui-Chun Yang; Ya-Nan Mi; Xin-Yu Gu; Jia-Ying Li; Ming-Xin Su (Journal of Environmental Management, 2026)

Tailoring the Si/Al ratio of Fe-SSZ-13 catalysts for enhanced catalytic N2O decomposition - Shujun Ming; Zhen Zhu; Lei Pang; Sheng Su; Xuannan Zhou; Feifei Xie; Shiya Pang; Yarong Fang; Tao Li (Journal of Environmental Chemical Engineering, 2026)

A methionine sulfoxide reductase A homolog gene(msrA1)deficiency significantly attenuates the virulence of Nocardia seriolae - Su-Ming Zhou; Yu Liu; Li-Yun Jin; Yuan Gao; Fei Yin (Fish & Shellfish Immunology, 2026)

Uncovering biogenic methane and vertical stratified cycling of elements in the Zhoushan offshore area - Xujia Ming; Hanghang Song; Qingfen Liu; Rongguo Su; Xianguo Li; Dahai Zhang (Estuarine, Coastal and Shelf Science, 2026)

Effective elimination of malachite green from solutions by functionalized hydrochar derived from co-hydrothermal carbonization of bamboo and polyvinyl chloride with ammonium persulfate assistance - Jia-Ming Zhao; Qian Zhang; Ying-Tao Su; Xiao-Man Huang; Bing Li (Chemical Engineering Journal, 2026)

Synthesis of Ti-based MXene from microwave pyrolysis of bamboo biomass for electromagnetic wave absorption - Su Wang; Shenghui Guo; Yong Li; Xiaolei Ye; Lei Gao; Li Yang; Ming Hou; Kaihua Chen; Jibiao Han; Yunchuan Li (Biomass and Bioenergy, 2026)

Discovery of FLF-15 as a novel selective inhibitor of ADAM17 to prevent hepatocellular carcinoma metastasis - Qing Li; Dao-ping Wang; Ting Zhong; Ai-ling Ling-hu; Jia-lin Chen; Fang Luo; Feng Zhang; Ming-zhi Su; Ying Yang; Yan-hua Fan (Molecular Diversity, 2026)

Long‐Term Dispersal Ability and Climate Drive Genetic and Biogeographic Divergence in Two Lizards With Contrasting Distribution Ranges - Shan Su; Wei Qian; Lu‐Wen Zhang; Xiang‐Mo Li; Li Ma; Xiao‐Ming Wang; Zheng‐Huan Wang; Xiang Ji (Journal of Biogeography, 2026)
Aims Long‐term dispersal ability fundamentally shapes genetic structure and biogeographic patterns, yet its role in driving divergence between closely related species with contrasting ranges remains less explored. Here, we assess its influence on genetic differentiation and range dynamics in two Eremias lizards, the widespread E. argus and the narrowly distributed E. brenchleyi . Location Northeast, Central North, and Northwest China. Taxon Mongolia racerunner Eremias argus and Ordos racerunner Eremias brenchleyi (Sauria: Lacertidae). Methods We sequenced two mitochondrial (COI and cyt b ) genes from 240 E. argus and 98 E. brenchleyi adults across their Chinese ranges, performed phylogenetic analyses using Maximum Likelihood and Bayesian Inference, assessed genetic diversity and differentiation via haplotype metrics and pairwise F ST , and projected suitable habitats under past, present and future climates using ensemble species distribution models (SDMs). Results The two species diverged approximately 4.28 million years ago. Eremias brenchleyi exhibited strong isolation‐by‐distance, high genetic differentiation, and limited post‐LGM (Last Glacial Maximum) demographic expansion, indicating topography‐constrained dispersal. In contrast, E. argus showed higher genetic connectivity and rapid expansion from the late LGM to the post‐glacial period. SDMs indicate that E. argus expanded following the LGM, while E. brenchleyi persisted in restricted ranges. By 2070, both species are projected to expand northward under SSP2‐4.5 and SSP5‐8.5, with E. brenchleyi benefiting more from warming in net range gain. Main Conclusions Long‐term dispersal ability, interacting with landscape and climate, drives genetic and biogeographic divergence. Eremias brenchleyi remains vulnerable to isolation and genetic erosion, while E. argus is threatened by climate‐driven range loss. Their contrasting responses underscore the necessity of integrating genetic and environmental data to understand species resilience under climate change.

Metabolic activation of pentachlorophenol: TCBQ as a potent inhibitor of gonadal steroidogenesis via 3β-hydroxysteroid dehydrogenase NAD+ binding-site thiolalkylation - Yao Lv; Jingwei Zhang; Ming Su; Shun Lu; Shaowei Wang; Ren-shan Ge; Huitao Li (Reproductive Toxicology, 2026)

Mechanistic insights into the enhancement of azithromycin biodegradation by extracellular polymeric substances: Roles of metabolic activity, electron transfer, and reactive oxygen species - Jian-Gang Zhou; Ming-Hong Wei; Shi-Jie Wang; Li Chen; Muhammad Wajid Ullah; Hong-Tao Liu; Su Sun (Journal of Hazardous Materials, 2026)

Metabolic mechanism of ethanol pre-fermentation to enhance anaerobic digestion of acidified food waste - Xudong Wang; Xujia Ming; Jiaqi Su; Mengyu Chen; Xianguo Li; Dahai Zhang (Journal of Cleaner Production, 2026)

Enhancement role of corncob slow-release carbon source on heterotrophic nitrification and aerobic denitrification process in low C/N wastewater treatment - Xin-Yu Gu; You-Wei Cui; Yuan Sui; Jia-Ying Li; Ming-Xin Su; Ze-You Lu; Rui-Chun Yang (Journal of Environmental Management, 2026)

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

Genome-wide analysis of Zoysia japonica REVEILLE family identifies ZjRVE8-1 as a positive cold-tolerance regulator - Cuiling Liu; Liangliang He; Ming Jiang; Zhihao Wu; Jieyi Li; Chao Liu; Quanrui Su; Jingyi Sun; Fei Xu; Shu Chen (Plant Cell Reports, 2026)

Field and laboratory investigations of the fluid in fully developed debris flows - Xiao Su; Ze-Min Xu; Yi-Xi Wen; Bin Li; Jing-Kai Meng; Lin Tian; Zi-Ming Ye; Gui-E Shi (Bulletin of Engineering Geology and the Environment, 2026)

Application of polyaluminum chloride and anionic polyacrylamide in the solid-liquid separation pretreatment of aquaculture tailwater - Jianping Xu; Yishuai Du; Hexiang Wang; Guogen Su; Jiawei Zhang; Fudi Chen; Ming Sun; Huiqin Tian; Li Zhou; Tianlong Qiu; Jianming Sun (Aquacultural Engineering, 2026)

Occurrences, profiles, and mass inventories of sediment p-phenylenediamine and their quinones in the northern South China Sea - Chan Liang; Ye-Yang Hou; Jin-Yun Li; Ying Guo; Xianghong Guan; Ming Su; Liang-Ying Liu; Eddy Y. Zeng (Marine Pollution Bulletin, 2025)

1-NP hijacks endocrine-metabolic checkpoints and disrupts testicular steroidogenesis by suppressing the cAMP-PKA-CREB-HMGCR axis - Xin-xin Zhu; Wei-wei Zhang; Ming-yue Hao; Zheng-ya Chen; Bai-fan Wan; Ming-hui Niu; Xiu-liang Li; Jian-hua Wei; Su-ya Liu; Shuang-ling Mi; Hua Wang; De-xiang Xu; et al. (Toxicology Letters, 2025)

Fully self-powered visualized droplet sensing system towards effective liquid analysis - Li Su; Jiacheng Liu; Yilong Yang; Ming Sun; Shuangyang Kuang; Yong Zhao (Chemical Engineering Journal, 2025)

Trend in chemical components and sources of PM2.5 and its relationship with ozone in central PRD, China (2018–2023) - Jianfan Yin; Shan Huang; Yunqian Liao; Zihan Li; Bin Yuan; Ming Chang; Weiwen Wang; Xiongzhou Lv; Xihua Li; Shuzhen Su; Xuemei Wang; Min Shao (Atmospheric Environment, 2025)

Neutrophil CD11b is a pivotal PANoptosis marker correlated with disease activity in antineutrophil cytoplasmic antibody-associated vasculitis - Xiang-Yu Han; Yi-Yang Zhao; Su-Fang Chen; Zhi-Ying Li; Ming-Hui Zhao; Min Chen (Apoptosis, 2025)

Serum cortisol and AdipoR2 rs12342 were involved in the correlation between stress and serum cholesterol in a gender-specific manner - Yi Lin Shen; Qi Wei Guo; Xue Cheng Li; Ke Xin Jia; Jun Yi Liu; Yan Zhi Yi; Jun Tao Ren; Jia Jing Cai; Guo Ming Su; Jia Lin; Ding Zhi Fang (Metabolic Brain Disease, 2025)

Modified Xiaoyao San ameliorates LPS-induced depression-like behavior by inhibiting NLRP3-mediated microglial pyroptosis - Lei Tian; Pan Su; Gang Feng; Shuaijun Peng; Liming Liu; Xiangli Yan; Xianghua Liu; Yucheng Li; Ming Bai; Baoying Wang; Erping Xu (Metabolic Brain Disease, 2025)

Genesis of the Pulang polymetallic mineralization system in Yunnan Province, China: Insights from in situ trace element and S isotope analyses of pyrite - Xiao-Yu Zhao; Zi-Chao Tang; Ming-Guo Deng; Wen-Chang Li; Jing-Wei Xu; Yan Su; Zhi-Peng Li; Lei Wang (Journal of Geochemical Exploration, 2025)

Unraveling Qu-aroma variation between inner and outer layers of medium-temperature Daqu: A multi-omics and sensory approach - Sheng-Bing Yang; Zhen-Ming Lu; Han-Jun Shen; Jun-Jie Fu; Yang Yang; Xiao-Juan Zhang; Li-Juan Chai; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

Experiment and theoretical analysis on the rotational behavior of mass glulam bolted and glued-in rod joints - Zheng Su; Ming Xu; Zhaoyan Cui; Ruixiong Li; Hongxin Liu (Engineering Structures, 2025)

CAR19-T/NK cell and circular aptamer–drug conjugate (ApDC) combination treatment increases immunotherapy efficacy - Ling-Qi Kong; Su-Yun Chen; Xu Cui; Ya-Hui Hu; Lian Wang; Jia-Yao Zhu; Lan-Xuan Guan; Bing-Kun Wang; Li-Ting Yang; Kai-Ming Chen; Chao-Ming Zhou (Molecular and Cellular Biochemistry, 2025)

Vegetation and climate change during the mid-late Holocene: A pollen record from the Arxan marshland in the Greater Khingan Mountains - Lisi Wei; Shoukang Su; Chunzhu Chen; Guoqiang Li; Ming Jin; Wei Xing; Ximing Zhang; Xuanru Cheng; Wenwei Zhao; Huan Li; Xiaojian Zhang; Yan Zhao (Journal of Mountain Science, 2025)

Human adenovirus in Taiwan, 2019–2023 - Su-Lin Yang; Wan-Ju Tsai; Chung-Hao Li; Yu-Hsin Cheng; Shu-Wei Lin; Ming-Tsan Liu; Fang-Tzy Wu (Archives of Virology, 2025)

Marine Hydrogen Pressure Reducing Valves: A Review on Multi-Physics Coupling, Flow Dynamics, and Structural Optimization for Ship-Borne Storage Systems - Heng Xu; Hui-Na Yang; Rui Wang; Yi-Ming Dai; Zi-Lin Su; Ji-Chao Li; Ji-Qiang Li (Journal of Marine Science and Engineering, 2025)
As a zero-carbon energy carrier, hydrogen is playing an increasingly vital role in the decarbonization of maritime transportation. The hydrogen pressure reducing valve (PRV) is a core component of ship-borne hydrogen storage systems, directly influencing the safety, efficiency, and reliability of hydrogen-powered vessels. However, the marine environment—characterized by persistent vibrations, salt spray corrosion, and temperature fluctuations—poses significant challenges to PRV performance, including material degradation, flow instability, and reduced operational lifespan. This review comprehensively summarizes and analyzes recent advances in the study of high-pressure hydrogen PRVs for marine applications, with a focus on transient flow dynamics, turbulence and compressible flow characteristics, multi-stage throttling strategies, and valve core geometric optimization. Through a systematic review of theoretical modeling, numerical simulations, and experimental studies, we identify key bottlenecks such as multi-physics coupling effects under extreme conditions and the lack of marine-adapted validation frameworks. Finally, we conducted a preliminary discussion on future research directions, covering aspects such as the construction of coupled multi-physics field models, the development of marine environment simulation experimental platforms, the research on new materials resistant to vibration and corrosion, and the establishment of a standardized testing system. This review aims to provide fundamental references and technical development ideas for the research and development of high-performance marine hydrogen pressure reducing valves, with the expectation of facilitating the safe and efficient application and promotion of hydrogen-powered shipping technology worldwide.

Debris aggregates in debris flows and implications for debris-flow dynamics - Yi-Xi Wen; Ze-Min Xu; Xiao Su; Bin Li; Zi-Ming Ye; Gui-E Shi; Jing-Kai Meng (Sedimentary Geology, 2025)

Synthesis and characteristics of amine-functionalized porous carriers for CO2 capture: A comprehensive review - Li Shen; Heping Liao; Haoxuan Liu; Fei Meng; Chang Su; Yi He; Ming Kong (Journal of Environmental Chemical Engineering, 2025)

Dynamic comparative analysis of moisture and flavour characteristics in green peppers (Piper nigrum L.) during thermal and non-thermal drying processes - Xinyi Wang; Yue Huang; Hui Su; Ying Lyu; Haiming Chen; Weijun Chen; Qiuping Zhong; Ming Zhang; Jianfei Pei; Rongrong He; Congfa Li; Wenxue Chen (Food Chemistry, 2025)

Comparison of the host-pathogen interactions between Pseudomonas plecoglossicida and Nocardia seriolea in a cell line derived from head kidney of yellow large croaker - Li-Yun Jin; Shu-Ya Li; Fei Yin; Zhen Tao; Xiao Xie; Su-Ming Zhou (Fish & Shellfish Immunology, 2025)

Impact of per- and polyfluoroalkyl substances exposure on renal dysfunction: Integrating epidemiological evidence with mechanistic insights - Weitao Su; Ziwen An; Yayuan Mei; Zhenzhen Tan; Zexuan Jiang; Xiuli Zeng; Zhiqiang Dong; Ming Yang; Jingtao Wu; Huicai Guo; Ang Li (Environmental Pollution, 2025)

Scale effects on buffeting response of long-span bridges - Yi Su; Mingshui Li; Jin Di; Rui Sun; Ming Li; Fengjiang Qin; Yan Jiang; Jie Wang (Engineering Structures, 2025)

Hierarchically shortened b-axis ZSM-5 nanosheet endows super catalytic stability for methanol-to-hydrocarbons reaction - Zhan Liu; Ying-Jun He; Zhi-Yi Hu; Jia-Min Lyu; Shen Yu; Yu-Hang Song; Xiao-Qiang Liao; Zhi-Wen Yin; Ming-Hui Sun; Yu-Chun Zhi; Li-Hua Chen; Bao-Lian Su (Chemical Engineering Journal, 2025)

Aptamer-anchored hydrophobic nanopores for electrochemical/fluorescent dual-mode identification of pathogenic bacteria - Jiangxue Dong; Tianyi Lu; Yufan Zhang; Ming Su; Jingjing Wang; Yajie Fan; Yanlei Li; Hongyuan Yan; Shigang Shen; Qun Ma; Zhongfeng Gao (Chemical Engineering Journal, 2025)

Interactions between soil and phyllosphere microbiomes modulate flavor formation of Qingxiang Tieguanyin Oolong Tea - Zhao Zhang; Xin-Rong Huang; Ming-Kang Jin; Le-Yang Yang; Jing-Jun Deng; Hu Li; Zhi-Ming Chen; Huo-Gui Su; Liang-De Xiao; Jin-Long Tang; Shun Li; Roy Neilson; et al. (Plant and Soil, 2025)

Association between per- and polyfluoroalkyl substances with serum hepatobiliary system function biomarkers in patients with acute coronary syndrome - Fang Xiao; Ming Yang; Junli Lv; Jing Li; Mingmei Guo; WenJing Duan; Haoran Li; Ziwen An; Zhengyi Su; Ang Li; Yi Liu; Jingchao Lu; et al. (Journal of Environmental Sciences, 2025)

Assessment of spatial and temporal variability in fecal contamination patterns within urbanized bay shellfish growing area utilizing community-based microbial source tracking approaches - Jiannan Lin; Hongxia Ming; Dongwei Li; Jiajie Li; Zhongzhi Chen; Ziqi Chen; Tingting Shi; Jie Su; Jingfeng Fan (Environmental Monitoring and Assessment, 2025)

Recyclable flame retardant, luminescent, and transparent thermoplastic polyurethanes: applications in light conversion films for flexible solar cells - Li-Wei Su; Ming-Hao Liu; Yang Jing; Peng-Yu Huang; Bo Jiang; Rui-Guang Xing; Xin Ge; Ya-Hui Li; Jin-Xiao Bao; Gao-Fei Pan (Chemical Engineering Journal, 2025)

A multi-objective evolutionary algorithm for adjustable-speed job shop scheduling with multi-trip automated guided vehicles constraints - Ming Lu; Chengjie Zhang; Gongfu Su; Long Chen; Ying Zou; Pei Li (Swarm and Evolutionary Computation, 2025)

Correction for calcium interference in the 40Ar/39Ar dating method - Wan-Feng Zhang; Jun-Jie Wang; De-Wen Zheng; Ming Xiao; Jia Zhang; Jun-Jie Li; Yu-Lian Zhang; Ying-De Jiang; Fei Su; Li Li; Yi-Gang Xu (Icarus, 2025)

Seismic behavior of CFST components for shear walls using double corrugated steel plates - Xu Liao; Xian Li; Wei Li; Rong Su; Ming Chen (Engineering Structures, 2025)

Polyphenylene molecular engineering enables highly efficient multi-resonance thermally activated delayed fluorescence emitters with quenching resistance - Longjiang Xing; Xiaofeng Wang; Xiaolong Liu; Wen-Cheng Chen; Shihao Liu; Siwei Chen; Mengke Li; Ji-Hua Tan; Jia-Ming Jin; Ruicheng Wang; Shangru Li; Shaomin Ji; et al. (Chemical Engineering Journal, 2025)

Characteristics and evolution of mass-transport complex since Late Miocene in the Zengmu and Beikang basins, southern South China Sea - Shuqin Huang; Ming Su; Haiteng Zhuo; Li Zhang; Shan Liu; Zhi Lin Ng; Zhixuan Lin; Boda Zhang; Kunwen Luo; Li’e Lin (Journal of Oceanology and Limnology, 2025)

Finite-time terminal sliding mode control strategy for the unmanned surface vehicle with composite disturbances - Yixin Su; Chenglong Gong; Zhengying Li; Danhong Zhang; Ming Xu (Ocean Engineering, 2025)

The effect of 254 nm ultraviolet C promoting ethanol-induced gastric injury healing - A potential physical factor therapy - Xiao Zhang; Dong-mei Li; Hong-long Chen; Xi-sheng Lin; Su-su Li; Le Yu; Nan Peng; Li-kang Wang; Na Wang; Yue-ming Gao (Journal of Photochemistry and Photobiology B: Biology, 2025)

Adsorptive-photocatalytic removal of organic dyes via biomass-derived nitrogen, oxygen-containing biochar-embedded Tin quantum dots catalyst - Hongxia Zhang; Meng Zhang; Wei Gao; Yang Liu; Jing Chen; Ming Zhong; Weiping Li; Bitao Su; Ziqiang Lei (Journal of Environmental Chemical Engineering, 2025)

Effects of homogenization and heat treatment on camel milk: Physicochemical properties, microstructure, and digestibility in infants - Na Su; Li Yi; Naihui Wang; Jing He; Liang Ming; Rendalai Si; Jiayu Zhang; Rimutu Ji (International Dairy Journal, 2025)

Rational design of phospholipase D to enhance thermostability and catalytic activity for efficient biocatalytic phosphatidylserine synthesis - Peng Zhang; Xin-An Mao; Xiao-Li Kong; Jin-Song Gong; Zi-Kai Wang; Chang Su; Heng Li; Xiao-Mei Zhang; Zhi-Ming Rao; Zheng-Hong Xu; Jin-Song Shi (Food Chemistry, 2025)

A novel electrochemical sensor for real-time quantitative monitoring of neuronal hydrogen peroxide under hypoxic conditions - Dan Su; Qianmin Li; Huihui Liang; Genhua Zhu; Ming Yang; Liangliang Liao; Zhaozhi Qiu; Youhui Zhang; Jiaquan Xu; Zhifu Ai; Yonggui Song (Chemical Engineering Journal, 2025)

Synergistic modulation of electronic structure in high entropy perovskite oxide for enhanced bifuntional oxygen evolution/reduction reactions and its mechanistic insights via in-situ analyses and density functional theory calculation - Thi Xuyen Nguyen; Chih-Heng Lee; Jun-Hong Sun; Chun-Kuo Peng; Wen-Hui Chu; Hamed Pourzolfaghar; Yu-Ru Lin; Muhammad Ghufron; Yuan-Yao Li; Yu-Hao Chang; Yan-Gu Lin; Hsin-Yi Tiffany Chen; et al. (Chemical Engineering Journal, 2025)

Redox state of NAD modulates the activation of Na-bicarbonate cotransporter NBCe1-B via IRBIT and L-IRBIT - Tianxiang Gui; Ying Liu; Mingfeng Fu; Han Wu; Pan Su; Xuhui Feng; Mengmeng Zheng; Zixuan Huang; Xudong Luo; Walter F. Boron; Li-Ming Chen (Science China Life Sciences, 2025)

Low-dose exposure to microplastics retards meiotic maturation via HDAC3 insufficiency - Qi Zhao; Ming Zong; Entong Song; Hongye Linghu; Xuanwen Li; Baicui Wang; Songling Xiao; Wanchun Guan; Jianzhong Su; Jiaming Zhang; Jingzhang Ji; Qingran Kong (Science China Life Sciences, 2025)

Geochemical constraints on the link between lunar magma ocean cumulates and the source of Chang'E-5 basalts from olivine trace element abundances - Yong Wu; Jie-Jun Jing; Zi-Ying Li; Ming-Kuan Qin; Ben-Xun Su; Jun Zhong; Dong-Fa Guo; Guang Fan; Rui-Ping Liu; Sheng He; Ting Li; Xiang-Kun Ge; et al. (Icarus, 2025)

Effects of Vibrio anguillarum Infection on Blood Homeostasis, Gut Microbiota and Transcriptome Profiling in Chinese Seabass (Lateolabrax maculatus) - Jiagen Ming; Dongyan Su; Xiufeng Han; Xiangyang Wu; Bo Li; Jiabo Tan; Xiaojun Song (Journal of Ocean University of China, 2025)

Probiotic potential of intestinal bacteria isolated from the digestive tract of hybrid snakehead (Channa argus♀ × Channa maculata♂) - Wen-Hao Wu; Yan-Xin Sun; Jia-Hao Zhang; Kun-Ming Huang; Xi-Chao Liu; Shu Tang; Wei Li; Biao Jiang; You-Lu Su (Aquaculture, 2025)

Identification of Potential Causal Genes for Neurodegenerative Diseases by Mitochondria-Related Genome-Wide Mendelian Randomization - Kang-Fu Yin; Ting Chen; Xiao-Jing Gu; Zheng Jiang; Wei-Ming Su; Qing-Qing Duan; Xiang-Jin Wen; Bei Cao; Ju-Rong Li; Li-Yi Chi; Yong-Ping Chen (Molecular Neurobiology, 2025)

U(VI) removal on polymer adsorbents: Recent development and future challenges - Yong-Gang Zhao; Li-Hui Chen; Ming-Li Ye; Wei-Si Su; Chao Lei; Xin-Jie Jin; Yin Lu (Critical Reviews in Environmental Science and Technology, 2025)

Regional disparities in PPCPs contamination of urban wastewater treatment plants: Unveiling influential factors and ecological effects - Xing Chen; Xiaofei Lu; Jiahua Peng; Guijin Su; Jing Meng; Qianqian Li; Yukang Hua; Ming Hu; Bin Shi (Environmental Pollution, 2025)

Effect of materials types of water-land junction settings on soil bacterial community structure in Shanghai riverside ecological corridor - Wei Guan; Songshuo Li; Qing Wang; Chenyan Sha; Jinghua Su; Min Wang; Ming Nie; Meng Lu (Ecological Engineering, 2025)

Research on the dielectric properties of flexible β-CD/PVDF all-organic films - Ming Wang; Hongwei Lu; Bengang Li; Shijia Yang; Weitao Su (Carbohydrate Polymers, 2025)

Enhancement of the yield of poly (ethylene terephthalate) hydrolase production using cell membrane protection strategy - Xiao-Qian Chen; De-Ming Rao; Xing-Yu Zhou; Yang Li; Xiao-min Zhao; De-min Kong; Han Xu; Chu-Qi Feng; Lei Wang; Ling-Qia Su; Zheng-Fei Yan; Jing Wu (Bioresource Technology, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Correlation analysis of transcriptome and metabolomics and functional study of Galactinol synthase gene (VcGolS3) of blueberry under salt stress - Fan Zhang; Tianjie Li; Longfei Gao; Dinakaran Elango; Jiaxin Song; Chaijing Su; Mingxuan Li; Weihua Zhang; Ming Chi; Xiaoyu Wang; Ying Wu (Plant Molecular Biology, 2025)

Biofilm formation comparison of Vibrio parahaemolyticus on stainless steel and polypropylene while minimizing environmental impacts and transfer to grouper fish fillets - Li-Ming Su; Rong-Tan Huang; Hsin-I Hsiao (International Journal of Food Microbiology, 2025)

Yeast community in the first-round fermentation of sauce-flavor Baijiu: Source, succession and metabolic function - Zheng-Pei Chen; Qian Cao; Tian-Tian Meng; Wei Shi; Xiao-Juan Zhang; Li-Juan Chai; Jin-Song Shi; Fu-Wei Chen; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Zhen-Ming Lu; et al. (Food Research International, 2025)

Development of a platform strain for integration expression of phospholipase D and its application in improving phosphatidylserine content of egg yolk - Peng Zhang; Xiao-Li Kong; Jin-Song Gong; Zhi-Yuan Yao; Chang Su; Heng Li; Xiao-Mei Zhang; Zhi-Ming Rao; Zheng-Hong Xu; Jin-Song Shi (Food Bioscience, 2025)

Identification and quantification of volatile organic compounds in Chinese recycled HDPE: Consequences for its applicability - Ming-Yue Zhang; Qi-Zhi Su; Qin-Bao Lin; Huai-Ning Zhong; Sheng Chen; Dan Li; Ben-Dong; Min-Qing Xu; Wei-Li Li (Food Packaging and Shelf Life, 2025)

Palaeowind reconstruction from Lower Cretaceous wave-dominated depositional records of the Tanan Depression, Northeast Asia - Xinyu Xue; Zaixing Jiang; Chao Liu; Li Wang; Huanyu Xie; Lizhou Song; Ming Su (Journal of Oceanology and Limnology, 2025)

The obesity-related mutation gene on nonalcoholic fatty liver disease - Yen-Yu Chen; Chi-Sheng Chen; Jee-Fu Huang; Wen-Hsiu Su; Chia-Yang Li; Wei-Shiun Chen; En-Sheng Lin; Wan-Long Chuang; Ming-Lung Yu; Shu-Chi Wang (Human Genetics, 2025)

Intramolecular distance-regulated G4 DNA enzymatic activity-based chromophotometric system for visual monitoring of diquat - Ya You; Wei-Guo Yang; Shun Zhang; Ming-Li Su; Qi-Lin Peng; Wan-Jiang Zhao; Ruo Yuan; Shang-Cheng Xu; Wen-Bin Liang (Analytica Chimica Acta, 2025)

Mitigating harmful cyanobacterial blooms in drinking water reservoirs through in-situ sediment resuspension - Jiao Fang; Yande Li; Ming Su; Tengxin Cao; Xufeng Sun; Yufan Ai; Jinyi Qin; Jianwei Yu; Min Yang (Water Research, 2024)

Research progress on iron-rich industrial waste as environmentally functional material - Xue Sun; Chenglei Hu; Tianguo Li; Jilai Zhang; Youbo Su; Ming Jiang (Sustainable Chemistry and Pharmacy, 2024)

Promotion of antibiotic-resistant genes dissemination by the micro/nanoplastics in the gut of snail Achatina fulica - Yan-Mei Da; Xiao-Ru Yang; Ming-Jun Li; Shun-Shun Li; Ze-Ping Gao; Ying Zhang; Jian-Qiang Su; Guo-Wei Zhou (Science of The Total Environment, 2024)

Early postnatal and concurrent exposure to metals and neurobehavioral outcomes at 5 years: Associations with individual environmental exposures and mixtures - Sui-Ling Liao; Shen-Hao Lai; Yuan-Ting Hsu; Li-Chen Chen; Ming-Han Tsai; Man-Chin Hua; Tsung-Chieh Yao; Kuan-Wen Su; Kuo-Wei Yeh; Chih-Yung Chiu; Shau-Ku Huang; Jing-Long Huang (NeuroToxicology, 2024)

Association between indoor PM2.5 components and accelerated biological aging in schizophrenia patients: Evidence from multi-omics mechanisms - Rubing Pan; Xingxu Yi; Yanlong Xu; Jian Song; Weizhuo Yi; Jintao Liu; Rong Song; Xuanxuan Li; Li Liu; Jiajun Yuan; Ning Wei; Yuxing Huang; et al. (Journal of Hazardous Materials, 2024)

Ultrasensitive detection of contaminants in milk using a novel NMS-Ag modified water-resistant paper substrate - Rui Su; Siqi Li; Yugang Su; Zhong Wang; Ming Gao (Food Chemistry, 2024)

Green fabrication of modified lignin/zeolite/chitosan-based composite membranes for preservation of perishable foods - Zhan-Chao Li; Meng-Yao Su; Xiao-Yu Yuan; Hai-Qing Lv; Rui Feng; Li-Jie Wu; Xiao-Ping Gao; Yan-Xia An; Zhan-Wei Li; Miao-Yun Li; Gai-Ming Zhao; Xiao-Peng Wang (Food Chemistry, 2024)

Improper toy waste handling can harm human health via seafood consumption: A comprehensive health risk assessment of heavy metals - Keqin Zhang; Jonathan Y.S. Leung; Chuanghong Su; Jinyan Liu; Jiufeng Li; Yinghua Chen; Jingchun Shi; Ming Hung Wong (Environmental Research, 2024)

High-level extracellular expression of phospholipase D by combinatorial fine-tuning strategy in Bacillus subtilis for efficient biosynthesis of phosphatidic acid - Peng Zhang; Xin-An Mao; Jin-Song Gong; Xiao-Li Kong; Chang Su; Xiao-Mei Zhang; Zhi-Ming Rao; Zheng-Hong Xu; Jin-Song Shi (Bioresource Technology, 2024)

Peroxynitrite-Triggered Carbon Monoxide Donor Improves Ischemic Stroke Outcome by Inhibiting Neuronal Apoptosis and Ferroptosis - Xin-Jian Guo; Lin-Yan Huang; Shi-Tong Gong; Ming Li; Wan Wang; Jie Chen; Yi-De Zhang; Xicun Lu; Xiaohua Chen; Lan Luo; Youjun Yang; Xiao Luo; et al. (Molecular Neurobiology, 2024)

Resistivity tomography based on multichannel electrodes - Fu-yu Jiang; Jiong Ni; Hai-jun Chen; Li-kun Gao; Song Chen; Xian-wei Wu; Zhi-qiang Su; Yao Lei; Ming-hui Dai; Run Han; Jun-kai Yu (Applied Geophysics, 2024)

Clostridium lamae sp. nov., a novel bacterium isolated from the fresh feces of alpaca - Xue Li; Ming Li; Weixiong Shi; Xia Li; Zhiguang Xiang; Lei Su (Antonie van Leeuwenhoek, 2024)

Establishment and Validation of Sandell-Kolthoff Method for Saliva Iodine Determination - Yue Su; Ming Li; Honglei Xie; Xin Hou; Meng Zhao; Jia Li; Haowen Pan; Zexu Zhang; Zongyu Yue; Wenjing Che; Lanchun Liu; Jiasen Cao; et al. (Biological Trace Element Research, 2024)

Decoding the Qu-aroma of medium-temperature Daqu starter by volatilomics, aroma recombination, omission studies and sensory analysis - Sheng-Bing Yang; Jun-Jie Fu; Jia-Huan He; Xiao-Juan Zhang; Li-Juan Chai; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Zhen-Ming Lu; Zheng-Hong Xu (Food Chemistry, 2024)

“Balloon-like” biomimetic erythrocyte vesicles potentiate photodynamic therapy for inducing immunogenic cell death - Zhiyin Li; Yikang Ji; Yue Su; Zijie Zhou; Xia Yang; Yu Huang; Ming Yan; Lingyue Shen (Chemical Engineering Journal, 2024)

Plasmonic honeycomb-like structures with Bernoulli effect and pre-activation effect for enhanced photocatalytic hydrogen production from waste water - Shaohui Guo; Xuchuan Cao; Jie Su; Jing Cui; Baichao Zhang; Chao Suo; Xiaochuan Duan; Xuanhua Li; Bingqing Wei; Xian-Ming Zhang (Chemical Engineering Journal, 2024)

Leaching-readsorption of VO43− optimized diffusion and adsorption of OH− on NiFeOOH catalytic interface for industrial water oxidation - Yu Ma; Mei-Xin Lin; Peng-Ji Su; Zi-Yi Gao; Xin Li; You-He Wang; Lian-Ming Zhao; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2024)

Inhibition of human and rat placental 3β-hydroxysteroid dehydrogenases by bisphenol A analogues depends on their hydrophobicity: In silico docking analysis - Shaowei Wang; Han Lu; Yingna Zhai; Yunbing Tang; Ming Su; Huitao Li; Yiyan Wang; Yi Liu; Ren-shan Ge (Chemico-Biological Interactions, 2024)

Concentration and activation biresponsive strategy in one analysis system with simultaneous use of G4 structure-specific signal probe and enzyme-catalyzed reaction - Yu-Shu Li; Chun-Feng Feng; Hao-Ran Chen; Wei-Guo Yang; Fei Liu; Ming-Li Su; Ruo Yuan; Li-Qun Zhang; Wen-Bin Liang (Analytica Chimica Acta, 2024)

Epidemiology of human metapneumovirus in Taiwan from 2013 to 2023 - Su-Lin Yang; Tai-Yuan Chiu; Kun-Lin Tsai; Chung-Hao Li; Jyh-Yuan Yang; Ming-Tsan Liu; Fang-Tzy Wu (Archives of Virology, 2024)

Comparative transcriptome analysis provides a glance into the regulatory of insulin-like peptide 1 gene in the Pacific white shrimp Litopenaeus vannamei - Manwen Su; Xiaojun Zhang; Xiaoxi Zhang; Jianbo Yuan; Ming Yang; Fuhua Li (Aquaculture, 2024)

Effects of socioeconomic status and regional inequality on the association between PM2.5 and its components and cardiometabolic multimorbidity: A multicenter population-based survey in eastern China - Zhiqian Cui; Xinxu Yi; Yuxin Huang; Ming Li; Zichen Zhang; Lingmei Kuang; Rong Song; Jintao Liu; Rubing Pan; Weizhuo Yi; Xiaoyu Jin; Jian Song; et al. (Science of The Total Environment, 2024)

BrARR10 contributes to 6-BA-delayed leaf senescence in Chinese flowering cabbage by activating genes related to CTK, GA and ABA metabolism - Ci-mei Wang; Ze-xiang Zeng; Zong-li Liu; Jian-hua Zhu; Xin-guo Su; Ri-ming Huang; Wei Wei; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen; Ying-ying Yang (Postharvest Biology and Technology, 2024)

Unified scheme design and control optimization of flapping wing for next-generation manta ray robot - Qi-meng Liu; Hao Chen; Peng-ming Guo; Guang-sheng Su; Wei-kun Li; Xin-yu Zeng; Di-xia Fan; Wei-cheng Cui (Ocean Engineering, 2024)

An effective strategy for synthesizing high-performance photocatalyst by recycling the graphite target wastes - Minghui Bai; Ruichong Chen; Xian Liu; Haoying Li; Jing Li; Heping Huang; Man Song; Qiuping Zhang; Yuanjie Su; Haomin Wang; Ming Xu; Guangzhong Xie (Journal of Environmental Chemical Engineering, 2024)

Development of a NiFe2O4 covalent organic framework based magnetic solid-phase extraction approach for specific capture of quinolones in animal innards prior to UHPLC–Q–Orbitrap HRMS detection - Shumin Lin; Yun-kai Lv; Aixue Zhu; Ming Su; Xiliang Li; Shu-xuan Liang (Food Chemistry, 2024)

Dual-Salt aqueous electrolyte for enhancing Charge-Storage properties of VO2 polymorphic cathodes for Zn-Ion batteries - Jing-Hong Huang; Xu-Feng Luo; Tzu-Yu Kuo; Yu-Hua Lai; Purna Chandra Rath; Chun-Wei Huang; Ming-Hsien Lin; An-Yuan Hou; Ju Li; Yu-Sheng Su; Wen-Wei Wu; Jeng-Kuei Chang (Chemical Engineering Journal, 2024)

Chloride homeostasis via enhanced salt ion secretion selectivity contributes to salt tolerance of recretohalophytic mangrove Avicennia marina - Qian-Su Ding; Chao-Qun Xu; Dong-Na Ma; Ming-Yue Wei; Chang-Hao Gao; Shan Zhang; Huan Li; Xue-Yi Zhu; Hai-Lei Zheng (Plant and Soil, 2024)

High-altitude exposure leads to increased modularity of brain functional network with the increased occupation of attention resources in early processing of visual working memory - Jing Zhou; Nian-Nian Wang; Xiao-Yan Huang; Rui Su; Hao Li; Hai-Lin Ma; Ming Liu; De-Long Zhang (Cognitive Neurodynamics, 2024)

Quantitative SERS detection of serum protein biomarkers for assessment of tumor microwave ablation outcomes - Yuzhen Ouyang; Wei Xie; Tian Tang; Xiaoming Su; Shasha Xiao; Zimo Liu; Ming Li; Minghua Wu; Jia Liu; Jia Luo; Pan Chen (Chemical Engineering Journal, 2024)

Three new isocoumarin analogues from an endolichenic fungus Aspergillus flavus CPCC 400810 - Ren-Zhong Wang; Bing-Jie Su; Yu-Chuan Chen; Tong-Mei Xiao; Bi-Ying Yan; Li-Yan Yu; Shu-Yi Si; De-Ling Wu; Ming-Hua Chen (Natural Product Research, 2024)

Towards long-term, high-accuracy, and continuous satellite total and fine-mode aerosol records: Enhanced Land General Aerosol (e-LaGA) retrieval algorithm for VIIRS - Lunche Wang; Xin Su; Yi Wang; Mengdan Cao; Qin Lang; Huaping Li; Junyao Sun; Ming Zhang; Wenmin Qin; Lei Li; Leiku Yang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

A full-parameter computational optimization of both injection parameters and injector layouts for a methanol/diesel dual-fuel direct injection compression ignition engine - Yaopeng Li; Yikang Cai; Ming Jia; Yang Wang; Xin Su; Laiqun Li (Fuel, 2024)

Multiple metabolite profiles uncover remarkable bioactive compounds and metabolic characteristics of noni fruit (Morinda citrifolia L.) at various stages of ripeness - Congyan Su; Ming Yang; Shuai Chen; Chuanxian Fu; Lin Zhang; Sixin Liu; Jiamu Kang; Congfa Li (Food Chemistry, 2024)

Investigation of water management for residential PEM fuel cells under ultra-low inlet pressure - Peiyi Liao; Daijun Yang; Pingwen Ming; Kefeng Hu; Guoqing Su; Siqi Chen; Meilin Pan; Zhilong Li (Chemical Engineering Journal, 2024)

Towards Stem/Progenitor Cell-Based Therapies for Retinal Degeneration - Hui Liu; Shuaiyan Lu; Ming Chen; Na Gao; Yuhe Yang; Huijuan Hu; Qing Ren; Xiaoyu Liu; Hongxu Chen; Qunyan Zhu; Shasha Li; Jianzhong Su (Stem Cell Reviews and Reports, 2024)

Heterometallic Eu/Zn-MOF-based ratiometric sensing platform: Highly sensitive fluorescence / second-order scattering identification of tetracycline analogs and its molecular informatization applications - Ya Jie Fan; Jiang Xue Dong; Tan Liu; Yan Qing Chang; Yong Sen Zhao; Yan Lei Li; Sai Mei Zhang; Song Yun Cao; Ming Su; Shi Gang Shen; Zhong Feng Gao (Analytica Chimica Acta, 2024)

Tuning multiple enzyme-like activities by metal doping for identification and quantitation of antioxidants in cosmetics - Sheng-Tao Wu; Hui-Qi Su; Kai-Lin Shen; Ying Li; Yi Ge; Xiu-Fang Cheng; Chang-Ming Nie; Cong-Hui Wang; Ying-Wu Lin (Chemical Engineering Journal, 2024)

Quantifying energy flexibility potential of ground electric vehicles in an airport with real behavior data - Xiaochen Liu; Ming Li; Xiaohua Liu; Tao Zhang; Zhi Fu; Zhihan Su; Rang Tu (Sustainable Cities and Society, 2024)

Coating seeds with biopolymers extracted from waste-activated sludge - Chen Shi; Shi-Chao Yuan; Lin Zhang; Xiang-Yang Wang; Li-Ting Hao; Shi-Ming Su; Zhongfang Lei; Xiao-Di Hao (Sustainable Chemistry and Pharmacy, 2024)

Exploring the chemical diversity of sesquiterpenes from the rarely studied south China sea soft coral Sinularia tumulosa assisted by molecular networking strategy - Sheng-Hui Zhu; Yuan-Min Chang; Song-Wei Li; Ming-Zhi Su; Li-Gong Yao; Lin-Fu Liang; Hong Wang; Yue-Wei Guo (Phytochemistry, 2024)

Anti-pancreatic cancer activity of cassane diterpenoids isolated from the seeds of Caesalpinia sappan mediated by autophagy activation via ROS/AMPK/mTORC1 pathway - Jia Su; De-Sheng Wang; Guo-Xian Hu; Yu-Yao Liu; Ming Hu; Ya Chen; Qi-Qi Wang; Run-Cheng Yan; Yun Wu; Yong-Jiao Li; Ke Ma; Yan-Yan Qi; et al. (Phytochemistry, 2024)

Isolation of 24-homoscalarane sesterterpenoids from a sponge of the genus Lendenfeldia - Li-Guo Zheng; You-Yan Chen; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; Yi-Hao Lo; Yu-Chi Tsai; Hao-Chun Hu; You-Ying Chen; Tsong-Long Hwang; Tzu-Ming Ou; Ping-Jyun Sung (Phytochemistry Letters, 2024)

Quercetin and Kaempferol inhibit HMC-1 activation via SOCE/NFATc2 signaling and suppress hippocampal mast cell activation in lipopolysaccharide-induced depressive mice - Pan Su; Zibo Li; Xiangli Yan; Baoying Wang; Ming Bai; Yucheng Li; Erping Xu (Inflammation Research, 2024)

Interactions between plants and bacterial communities for phytoremediation of petroleum-contaminated soil - Ming Zhong; Caiyu Yang; Liping Su; Ziyu Sun; Juanjuan Xu; Jin Zhang; Qilong Li; Yimin Hao; Hui Ma; Hongman Chen; Jiamei Chen; Shuisen Chen (Environmental Science and Pollution Research, 2024)

Antihypertensive treatment during pregnancy induces long-term changes in gut microbiota and the behaviors of the attention deficit hyperactivity disorder offspring - Hong-Bao Li; Meng-Lu Xu; Wen-Jie Xia; Yuan-Yuan Dong; Bo Peng; Qing Su; Xiao-Min Wang; Jia-Yue Yu; Ya-Nan Gao; Jun-Zhe Wu; Meng-Yue Xu; Jin-Bao Yang; et al. (Toxicology and Applied Pharmacology, 2024)

Identification and molecular docking of a novel antidiabetic peptide from protamex-camel milk protein hydrolysates against α-amylase and DPP-IV - Na Su; Li Yi; Jing He; Liang Ming; Tuyatsetseg Jambal; Batmunkh Mijiddorj; B. Maizul; Ts. Enkhtuul; Rimutu Ji (International Dairy Journal, 2024)

E-eye and FT-NIR combined with multivariate algorithms to rapidly evaluate the dynamic changes in the quality of Gastrodia elata during steaming process - Jiu-ba Zhang; Bin Wang; Yun-fei Zhang; Yi Wu; Ming-xuan Li; Ting Gao; Tu-lin Lu; Zhen-hua Bian; Lian-lin Su (Food Chemistry, 2024)

2D ZIF-8 derived N-doped porous carbon nanosheets for high-performance Li-Se batteries - Xu-Wei Luo; Ming-Ran Zhou; Mao-Jin Ran; Dao-Xiang Xun; Jia-Le He; Zhi-Yi Hu; Hemdan S.H. Mohamed; Jing Liu; Li-Hua Chen; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2024)

Initial study and phylogenetic analysis of hard ticks (Acari: Ixodidae) in Nantong, China along the route of avian migration - Jian-Ming Yuan; Jing Su; Zhi-Hai Zhang; Bin Sun; Xue-Li Jiao; Xin Zhang; Yun-Peng Zhai; Yu-Jie Chen (Experimental and Applied Acarology, 2024)

A new insight on the xyl upper operon revealed through genomic investigation strategy - Xuefeng Tian; Shaojing Wang; Peishan Chen; Mingbo Yang; Zhaoying Su; Yue Ming; Guoqiang Li; Ting Ma (International Biodeterioration & Biodegradation, 2024)

SERS lateral flow strip detection of serum biomarkers for noninvasive assessment of operative microwave ablation outcomes of unresectable hepatocellular carcinoma - Xiaoming Su; Xinyu Liu; Yuzhen Ouyang; Yangcenzi Xie; Mingyang Chen; Pan Chen; Jia Liu; Minghua Wu; Chien-hong Lin; Hong Zhong; Ming Li (Chemical Engineering Journal, 2024)

Four uncommon cycloamphilectane-type diterpenoids with antibacterial activity from the South China Sea soft coral Sinularia brassica - Zi-Yi Xia; Man-Man Sun; Yang Jin; Ming-Zhi Su; Song-Wei Li; Hong Wang; Yue-Wei Guo (Phytochemistry, 2024)

Influence on the volatilization of ethyl esters: Nonnegligible role of long-chain fatty acids on Baijiu flavor via intermolecular interaction - Qing-Ru Liu; Xian-Li Lin; Zhen-Ming Lu; Li-Juan Chai; Song-Tao Wang; Jin-Song Shi; Su-Yi Zhang; Cai-Hong Shen; Xiao-Juan Zhang; Zheng-Hong Xu (Food Chemistry, 2024)

Green space and its types can attenuate the associations of PM2.5 and its components with prediabetes and diabetes—— a multicenter cross-sectional study from eastern China - Zhiqian Cui; Rubing Pan; Jintao Liu; Weizhuo Yi; Yuxin Huang; Ming Li; Zichen Zhang; Lingmei Kuang; Li Liu; Ning Wei; Rong Song; Jiajun Yuan; et al. (Environmental Research, 2024)

Methyl jasmonate regulation of pectin polysaccharides in Cosmos bipinnatus roots: A mechanistic insight into alleviating cadmium toxicity - Chun-Yu Fan; Xiao-Fang Yu; Yu-Jia Liu; Xiao-Xuan Zeng; Fu-Wen Luo; Xian-Tong Wang; Xuan Yang; Xiao-Yu Wang; Xiao Xue; Li-Juan Yang; Ting Lei; Ming-Yan Jiang; et al. (Environmental Pollution, 2024)

Iodine Acetonitrile as a Drinking Water Disinfectant Showed a Potential Toxic Effect on Organism - Ya-Ping Li; Jie-Wen Cai; Pin-Ying Su; Shi-Ming Xie; Jia-Xuan Lai; Zi-Ru Xian; Jing-Da Qiao (Water, Air, & Soil Pollution, 2024)

Hydrothermal synthesis of lanthanum oxide nanoparticles modified pumice: High lanthanum oxide loading ratio and efficiency phosphate removal - Yi-Fan Xiao; Yong Zhang; De-Cai Wang; Yu-Ming Su; Jing Wu; Jia-Qi Liu; Li-Li Yang; Zhen Jin (Journal of Environmental Chemical Engineering, 2024)

Chalcones from plants cause toxicity by inhibiting human and rat 11β-hydroxysteroid dehydrogenase 2: 3D-quantitative structure-activity relationship (3D-QSAR) and in silico docking analysis - Hang Lin; Ming Su; Chao Wen; Yunbing Tang; Huitao Li; Yandan Wu; Ren-shan Ge; Xing-wang Li; Han Lin (Food and Chemical Toxicology, 2024)

A proposed framework for a social-ecological traits database for studying and managing urban plants and assessing the potential of database development using Floras - Chi-Ru Chang; Mong-Huai Su; Yi-Hsuan Li; Ming-Chun Chen (Urban Forestry & Urban Greening, 2024)

Quaternary stratigraphic architecture of the Pearl River Mouth continental shelf, northern South China Sea: Unraveling stratigraphic imprints of tectonism, paleoceanography, and climate change - Haiteng Zhuo; Xin Nie; Ming Su; Wei Zhou; Yaping Lei; Yingmin Wang; Xuechao Peng; Yan Qiu; Weiyao Yan; Li'e Lin (Sedimentary Geology, 2024)

Generation and origin of persistent high excess pore water pressure in debris flows - Zi-Ming Ye; Ze-Min Xu; Bin Li; Xiao Su; Gui-E Shi; Jing-Kai Meng; Lin Tian (Geomorphology, 2024)

A multifunctional emitter with synergistical adjustment of rigidity and flexibility for high-performance data-recording and organic light-emitting devices with “hot exciton” channel - Guowei Chen; Wen-Cheng Chen; Yaozu Su; Ruicheng Wang; Jia-Ming Jin; Hui Liang; Bingxue Tan; Dehua Hu; Shaomin Ji; Hao-Li Zhang; Yanping Huo; Yuguang Ma (Chemical Engineering Journal, 2024)

The incidence of asthma attributable to temperature variability: An ecological study based on 1990–2019 GBD data - Qingsong Xu; Qinfeng Zhou; Junjun Chen; Tong Li; Junxiong Ma; Runming Du; Mintao Su; Jing Li; Ming Xu; Shengzhi Sun; Jing Ma; Murugappan Ramanathan; et al. (Science of The Total Environment, 2023)

Seroprevalence and potential risk factors of brucellosis in sheep from America, Africa and Asia regions: A systematic review and meta-analysis - Lian-Min Li; Qi Wang; Jun-Feng Shi; Ting Li; Bo Zhao; Qing-Xia Ma; Hong-Ying Liu; Nuo Su; Ruo-Peng Cai; Fan-Li Zeng; Qing-Long Gong; Kun Shi; et al. (Research in Veterinary Science, 2023)

Evaluation of the prediction performance of air quality numerical forecast models in Shenzhen - Chanfang Liu; Chengyu Wu; Xinyuan Kang; Hanlu Zhang; Qing Fang; Yueyuan Su; Zhiyong Li; Yujing Ye; Ming Chang; Jianfeng Guo (Atmospheric Environment, 2023)

A Stable Irinotecan Liposome with Enhanced Antitumor Activity in a Range of Tumor Models - Zhengxing Su; Li Li; Fei Hao; Jinlong Zhao; Ming Li; Xi Zhao; Dong Zhao (Pharmaceutical Research, 2023)

Epidemiological analysis of drinking water-type fluorosis areas and the impact of fluorosis on children’s health in the past 40 years in China - Feiqing Wang; Yanju Li; Dongxin Tang; Jianing Zhao; Bo Yang; Chike Zhang; Min Su; Zhixu He; Xiaodong Zhu; Dong Ming; Yang Liu (Environmental Geochemistry and Health, 2023)
This study analyzed the effect of China’s fluorosis prevention and control program, which has been in effect for more than 40 years, and the impact of fluorosis on children’s health. Relevant research studies were retrieved from the following online databases from the time of their inception to May 2022: PubMed, ScienceDirect, Embase, Cochrane, China National Knowledge Infrastructure, and Wanfang. The Review Manager 5.3 software was used in statistical analyses. This article included seventy studies: Thirty-eight studies reported the effect of improving water quality and reducing fluoride content, the incidence rate of dental fluorosis in children, and the level of urinary fluoride, and thirty-two studies reported the intelligence quotient (IQ) and health status of children. Following water improvement strategies, the fluoride levels in drinking water decreased significantly; urinary fluoride levels and dental fluorosis decreased significantly in children. With regard to the effect of fluorosis on the IQ of children, the results showed that the IQ of children in areas with a high fluoride of fluorosis was lesser than that in areas with a low fluoride, and this difference was significant. Based on the prevalence of dental fluorosis and its effect on the intelligence of children, it appears that reducing fluoride levels in drinking water and monitoring water quality are important strategies for the prevention and treatment of fluorosis. Graphical abstract

Perovskites with narrow quantum-wells distribution and thermally activated energy funneling for sky-blue light-emitting diodes - Guanwei Sun; Weidong Qiu; Jiayu Li; Shuai Zhang; Zijian Chen; Denghui Liu; Chenyang Shen; Tao Wen; Zhe Liu; Junrong Pu; Zhihai Yang; Guo-xi Yang; et al. (Chemical Engineering Journal, 2023)

JcSEUSS1 negatively regulates reproductive organ development in perennial woody Jatropha curcas - Jingxian Wang; Xue Bai; Yiqing Su; Hongjun Deng; Li Cai; Xin Ming; Yan-Bin Tao; Huiying He; Zeng-Fu Xu; Mingyong Tang (Planta, 2023)

HVT-vectored H7 vaccine protects chickens from lethal infection with the highly pathogenic H7N9 Avian inﬂuenza virus - Yi-qun Chen; Guan-ming Su; Jia-hao Zhang; Bo Li; Kai-xiong Ma; Xu Zhang; Li-hong Huang; Ming Liao; Wen-bao Qi (Veterinary Microbiology, 2023)

Intelligent marine area supervision based on AIS and radar fusion - Wang Chi Ming; Li Yanan; Min Lanxi; Chen Jiuhu; Lin Zhong; Su Sunxin; Zhang Yuanchao; Chen Qianying; Chen Yugui; Duan Xiaoxue; Wei Jiayi; Zhu shunzhi (Ocean Engineering, 2023)

E-eye, flash GC E-nose and HS-GC-MS combined with chemometrics to identify the adulterants and geographical origins of Ziziphi Spinosae Semen - Jiu-ba Zhang; Ming-xuan Li; Yun-fei Zhang; Yu-wen Qin; Yu Li; Lian-lin Su; Lin Li; Zhen-hua Bian; Tu-lin Lu (Food Chemistry, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Trichlorfon blocks androgen synthesis and metabolism in rat immature Leydig cells - Huan Chen; Yaoyao Dong; Huitao Li; Zhili Chen; Ming Su; Qiqi Zhu; Ren-Shan Ge; Xinjun Miao (Reproductive Toxicology, 2023)

Innovation policy and ecological welfare performance: evidence from a quasi-natural experiment of China - Yutong Su; Wenqi Li; Ming Chen; Chengfeng Wu; Xin Tan (Environmental Science and Pollution Research, 2023)

Quantifying source effects based on rainwater δ18O from 10-year monitoring records in Southwest China - Yan-Xia Xue; Jian Zhang; Zhen Su; Yao Wu; Qi-sheng Liang; Ming-Qiang Liang; Xiang-Zhuo Liu; Chao-Jun Chen; Hai-Ying Qiu; Jun-Yun Li; Ting-Yong Li (Applied Geochemistry, 2023)

Determinants affecting the blood mercury levels of preschool children in Shanghai, China: A cross-sectional study - Xi Xu; Yu-Qing Wang; Chen-Yin Dong; Chun-Ping Hu; Li-Na Zhang; Zhen-Yan Gao; Min-Ming Li; Su-Su Wang; Chong-Huai Yan (Environmental Science and Pollution Research, 2023)

Ocellatuspyrones A‒G, new antibacterial polypropionates from the Chinese mollusk Placobranchus ocellatus - Song-Wei Li; Dan-Dan Yu; Ming-Zhi Su; Li-Gong Yao; Hong Wang; Xueting Liu; Yue-Wei Guo (Marine Life Science & Technology, 2023)
Marine invertebrates serve as rich sources of secondary metabolites with intriguing chemical diversities and a wide spectrum of biological activities. Particularly, marine shell-less sacoglossan mollusks have attracted much attentions due to the fact that mollusks apply complex metabolites as chemical defense agents against to their predators. With the purpose of discovering bioactive secondary metabolites to develop marine-derived medicines from the South China Sea, we have conducted a chemical study on the photosynthetic mollusk Placobranchus ocellatus. As a result, seven new γ -pyrone polypropionates, namely ( ±)-ocellatuspyrone A ( 1 ), ( ±)-ocellatuspyrone B ( 2 ), and ocellatuspyrones C−G ( 5 , 9 − 12 ), along with five known polypropionates, have been isolated and characterized from the South China Sea photosynthetic mollusk Placobranchus ocellatus . Extensive spectroscopic analysis, single crystal X-ray diffraction analysis, modified Mosher’s method, ECD comparison, CD exciton chirality method, TDDFT-ECD calculation, and chemical conversion were used to determine the structures and absolute configurations of the new compounds and the stereochemistry of undefined known compounds 4 , 6 and 7 . All these isolated polypropionates were evaluated in bioassays for their biological activities, including antibacterial, neuroprotective effect, anti-inflammatory, PTP1B inhibitory, and antiviral activities. Compounds 7 , 8 and 11 were found for the first time to show antibacterial activity against fish pathogenic bacteria Streptococcus parauberis (the main pathogen causing fish streptococcal infections and acute death) with MIC values of 35.8, 34.2, and 37.4 μg/mL, respectively, which might be potential novel antibacterial agents for the treatment of fish infectious diseases.

Simulation of anaerobic co-digestion of steam explosion pulping wastewater with cattle manure: Focusing on degradation and inhibition of furfural - Pengfei Li; Xinyu Wei; Ming Wang; Di Liu; Jie Liu; Zhanjiang Pei; Fengmei Shi; Su Wang; Xin Zuo; Dan Li; Hongjiu Yu; Nan Zhang; et al. (Bioresource Technology, 2023)

Recycling of steel slag as an alkali activator for blast furnace slag: geopolymer preparation and its application in composite cement - Qiang Wang; Hui-li Su; Chuan-ming Li; Xian-jun Lyu (Clean Technologies and Environmental Policy, 2023)

Aerobic biodegradation of quinoline under denitrifying conditions in membrane-aerated biofilm reactor - Hailong Tian; Yuanyuan Li; Hui Chen; Jisheng Zhang; Ming Hui; Xingjian Xu; Qingxian Su; Barth F. Smets (Environmental Pollution, 2023)

High entropy promoted active site in layered double hydroxide for ultra-stable oxygen evolution reaction electrocatalyst - Thi Xuyen Nguyen; Chia-Chien Tsai; Van Thanh Nguyen; Yan-Jia Huang; Yen-Hsun Su; Siang-Yun Li; Rui-Kun Xie; Yu-Jung Lin; Jyh-Fu Lee; Jyh-Ming Ting (Chemical Engineering Journal, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

Extracellular Vesicles Derived from Bone Mesenchymal Stem Cells Carrying circ_0000075 Relieves Cerebral Ischemic Injury by Competitively Inhibiting miR-218-5p and Up-regulating E3 Ubiquitin Ligase SMURF2 - Yue Liu; You-Ping Li; Li-Min Xiao; Li-Ke Chen; Su-Yue Zheng; Er-Ming Zeng; Chun-Hua Xu (Molecular Neurobiology, 2023)

Comparative genomics revealed that Vibrio furnissii and Vibrio fluvialis have mutations in genes related to T6SS1 and T6SS2 - Jiakai Sun; Haochen Su; Wenhui Zhang; Xuesong Luo; Ruichao Li; Ming Liu (Archives of Microbiology, 2023)

Bacteroides rhinocerotis sp. nov., isolated from the fresh feces of rhinoceros in Beijing Zoo - Xue Li; Peilin Sun; Liang Gong; Weixiong Shi; Zhiguang Xiang; Ming Li; Lei Su; Chuan Qin (Archives of Microbiology, 2023)

Lactococcus intestinalis sp. nov., a new lactic acid bacterium isolated from intestinal contents in Alzheimer’s disease mice - Peilin Sun; Xue Li; Weixiong Shi; Ling Zhang; Ming Li; Lei Su; Chuan Qin (Antonie van Leeuwenhoek, 2023)

Biofilter-constructed wetland-trophic pond system: A new strategy for effective sewage treatment and agricultural irrigation in rural area - Xinxin Peng; Wei Yang; Qiu Jin; Shihua Su; Pan Guo; Ming Li; Huazu Liu; Wei Li (Journal of Environmental Management, 2023)

Relationship between the effects of heat pre-treatment on anaerobic performance of pig manure and the microbial variation within reactors - Ming Wang; Jianlin Wang; Kai Liu; Qichen Li; Wenzhe Li; Jinxia Fan; Su Wang; Fengmei Shi; Xin Zuo; Pengfei Li (Chemical Engineering Journal, 2023)

Evidence of hydrothermal fluid migration pathways in pores and microfractures based on nuclear magnetic resonance and electron microscopic analyses from the Southwest Indian Ridge - Qianyu Li; Chao Chen; Chunhui Tao; Tao Wu; Jianping Zhou; Zhaoyang Su; Zhongmin Zhu; Long Liu; Tianyu Jie; Ming Chen (Marine Geology, 2023)

Distribution patterns of landslides triggered by the 2022 Ms 6.8 Luding earthquake, Sichuan, China - Jian-qiang Zhang; Zong-ji Yang; Qing-kai Meng; Jiao Wang; Kai-heng Hu; Yong-gang Ge; Feng-huan Su; Bo Zhao; Bo Zhang; Ning Jiang; Yu Huang; Zai-yang Ming; et al. (Journal of Mountain Science, 2023)

The galU gene is required for in vivo survival of pseudomonas plecoglossicida in large yellow croaker ( Larimichthys crocea ) - Feng‐Ling Shu; Li‐Yun Jin; Hao Liu; Zhen Tao; Fei Yin; Jia‐Song Xie; Su‐Ming Zhou (Journal of Fish Diseases, 2023)
Pseudomonas plecoglossicida is an important pathogenic bacterium in aquaculture that causes visceral granulomas in large yellow croaker ( Larimichthys crocea ). Uridine diphosphate glucose phosphorylase encoded by galU plays a key role in biosynthesis of the bacterial envelope, particularly lipopolysaccharide and the capsule. In this study, we inactivated the galU gene in the P. plecoglossicida isolate XSDHY‐P. The galU mutant strain showed impaired growth in the early exponential stage and lacked the O polysaccharide side chain in lipopolysaccharide, but almost no defect in biofilm formation was detected. The galU mutant strain also exhibited significantly more sensitivity to the bactericidal action of normal fish serum mediated by the complement system compared to the wild‐type strain. In a cell model originating from the head kidney of large yellow croaker, the galU mutant strain showed lower capacities of adhesion, invasion, and intracellular survival compared to the wild‐type strain. In addition, the deficiency of the galU mutant drastically decreased bacterial loads in tissues and attenuated P. plecoglossicida virulence in fish. These results suggest that the galU gene of P. plecoglossicida is required for in vivo survival in large yellow croaker.

Prediction of diffuse solar radiation by integrating radiative transfer model and machine-learning techniques - Yunbo Lu; Renlan Zhang; Lunche Wang; Xin Su; Ming Zhang; Huaping Li; Shiyu Li; Jiaojiao Zhou (Science of The Total Environment, 2023)

Evaluating the influence of gradient applied voltages on electro-enhanced sequence batch reactor treating aniline wastewater: System performance, microbial community and functional genes - Jing He; Qian Zhang; Meng Li; Tingzhen Ming; Jiapeng Feng; Haojin Peng; Junhao Su; Yunjie Zhang (Journal of Cleaner Production, 2023)

Gel properties of soy protein isolate-potato protein-egg white composite gel: Study on rheological properties, microstructure, and digestibility - Yuanqi Lv; Lilan Xu; Tingting Tang; Junhua Li; Luping Gu; Cuihua Chang; Ming Zhang; Yanjun Yang; Yujie Su (Food Hydrocolloids, 2023)

Sesamol alleviates manganese-induced neuroinflammation and cognitive impairment via regulating the microglial cGAS-STING/NF-κB pathway - Jinxia Wu; Honggang Chen; Tingting Guo; Ming Li; Changhao Yang; Michael Aschner; Jingyuan Chen; Peng Su; Wenjing Luo (Environmental Pollution, 2023)

Ultrafast organic solvent nanofiltration in C C bonded conjugated microporous membrane-based nanochannels by space-confined polymerization - Qianwen Su; Yinying Wang; Jinghao Chen; Daohui Zhao; Huali Long; Ming Li (Chemical Engineering Journal, 2023)

A novel bifunctional zinc gluconate electrolyte for a stable Zn anode - Xuena Xu; Ming Song; Min Li; Yan Xu; Limei Sun; Liluo Shi; Yaqiong Su; Chao Lai; Chao Wang (Chemical Engineering Journal, 2023)

Enhanced stability and combustion performance of AlH3 in combination with commonly used oxidizers - Ming-Hui Yu; Su-Lan Yang; Wu-Xi Xie; Zhao-Yang Zhu; He-Ping Li; Qi-Long Yan (Fuel, 2023)

microRNAs shape social immunity: a potential target for biological control of the termite Reticulitermes chinensis - Long Liu; Feng-Ming Yan; Chen-Chen Zhao; Li-Juan Su; Qiu-Ying Huang; Qing-Bo Tang (Journal of Pest Science, 2023)
Eusocial insects can employ various behavioural and physiological disease defences to avoid, resist and tolerate pathogen infections in their closely related and packed colonies, termed social immunity. Recent studies have shown that several molecules serve insect social immunity, including chemical odours, insect venoms, immune-related proteins, etc. However, whether and how microRNAs (miRNAs), whose precursors are processed by Dicer-1 , drive social immunity in insect colonies is still unknown. Here, we used a ‘host–pathogen’ system (host: Reticulitermes chinensis ; pathogen: Metarhizium anisopliae ) to explore the impact of miRNAs on social immunity in termite colonies. We found that RNAi-mediated silencing of Dicer-1 led to decreased miRNA concentration, significantly inhibited carbohydrate and energy metabolism and affected other life processes, such as the immune response and oxidation–reduction reactions, in whole body of the termite. In behavioural defence, silencing Dicer-1 significantly diminished defensive social behaviours such as locomotion, grooming, cannibalism and burial in termite groups when encountering fungal contamination. In physiological defence, Dicer-1 silencing and miR-71-5 stimulation resulted in significantly decreased antifungal activities of termites. Furthermore, both Dicer-1 -silenced and miR-71-5 stimulant-treated termite groups exhibited a high level of mortality during fungal contamination. Our findings demonstrated the important role of miRNAs in shaping social immunity in termite colonies, providing insights necessary to understand the potential mechanisms underlying behavioural and physiological disease defences in insects and hence laying the groundwork for miRNA-based pest control.

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

AIoT-Based Ergometer for Physical Training in Frail Elderly with Cognitive Decline: A Pilot Randomized Control Trial - Chih-Chun Lin; Li-Chieh Kuo; Yu-Sheng Lin; Chia-Ming Chang; Fang Wen Hu; Yi-Jing Chen; Chun-Tse Lin; Fong-Chin Su (Journal of Medical and Biological Engineering, 2022)
Purpose Reduced physical activity is reported in the elderly, especially in institutional residents. Institutionalized older adults exhibit a high prevalence of frailty. In this work, we developed an artificial intelligence of things (AIoT)-based feedback assistive strengthening ergometer (AIFASE), for the physical strengthening of the elderly with intelligent assistance. Methods We conducted a 12-week intervention in a long-term care facility. In total, 16 participants (84.38 ± 6.0 years; 4 males and 12 females) were recruited with 1:1 randomization of exercise to control groups. The muscle strength of the lower extremities, timed up and go test (TUG), and Short-form Physical Performance Battery (SPPB) of the participants were measured. The AIFASE system allows the clinical staff to record the personal physical performance of the elderly and generates personalized exercise prescriptions accordingly. AIFASE also displays the current usage status of all ergometers and the users’ physiological conditions. The algorithms were developed to generate warning alerts when the training workload was too large by personal physiological detection. AIFASE automatically customized the exercise prescription according to the user’s exercise performance. Results After a 12-week AIFASE intervention, the intervention group exhibited significant improvements in the strength of the hip flexor, Semi-Tandem Stand, and Tandem Stand. Conclusion In this study, we developed an AIoT ergometer that delivered customized physical training prescriptions to improve the physical performance of long-term care facility residents. We believe that the application of AIFASE will help improve the quality of institutional care.

Genistein Alleviates Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus by Activating the Sirt1/Nrf2 Pathway in High Salt-Induced Hypertension - Li-Gang Niu; Na Sun; Kai-Li Liu; Qing Su; Jie Qi; Li-Yan Fu; Guo-Rui Xin; Yu-Ming Kang (Cardiovascular Toxicology, 2022)

Two new aromatic derivatives from Codonopsis pilosula and their α-glucosidase inhibitory activities - Ru-Yue Wang; Pan-Jie Su; Bing Li; Xiao-Qing Zhan; Feng-Ming Qi; Chun-Wei Lv; Fang-Di Hu; Kun Gao; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

Exploration of the amino acid metabolic signature in anthracycline-induced cardiotoxicity using an optimized targeted metabolomics approach based on UPLC-MS/MS - Wendi Li; Shanshan Li; Zhenju Cao; Yi Sun; Wei Qiu; Mei Jia; Ming Su (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)

Hypofunction of directed brain network within alpha frequency band in depressive patients: a graph-theoretic analysis - Shuang Liu; Sitong Chen; Zhenni Huang; Xiaoya Liu; Meijuan Li; Fangyue Su; Xinyu Hao; Dong Ming (Cognitive Neurodynamics, 2022)
Directed brain networks may provide new insights into exploring physiological mechanism and neuromarkers for depression. This study aims to investigate the abnormalities of directed brain networks in depressive patients. We constructed the directed brain network based on resting electroencephalogram for 19 depressive patients and 20 healthy controls with eyes closed and eyes open. The weighted directed brain connectivity was measured by partial directed coherence for α, β, γ frequency band. Furthermore, topological parameters (clustering coefficient, characteristic path length, and et al.) were computed based on graph theory. The correlation between network metrics and clinical symptom was also examined. Depressive patients had a significantly weaker value of partial directed coherence at alpha frequency band in eyes-closed state. Clustering coefficient and characteristic path length were significantly lower in depressive patients (both p < .01). More importantly, in depressive patients, disruption of directed connectivity was noted in left-to-left ( p < .05), right-to-left ( p < .01) hemispheres and frontal-to-central ( p < .01), parietal-to-central ( p < .05), occipital-to-central ( p < .05) regions. Furthermore, connectivity in LL and RL hemispheres was negatively correlated with depression scale scores (both p < .05). Depressive patients showed a more randomized network structure, disturbed directed interaction of left-to-left, right-to-left hemispheric information and between different cerebral regions. Specifically, left-to-left, right-to-left hemispheric connectivity was negatively correlated with the severity of depression. Our analysis may serve as a potential neuromarker of depression.

Intestinal Models for Personalized Medicine: from Conventional Models to Microfluidic Primary Intestine-on-a-chip - Xiang-Guang Li; Ming-xia Chen; Su-qing Zhao; Xiu-qi Wang (Stem Cell Reviews and Reports, 2022)

Aquapteridospora jiangxiensis, a new aquatic hyphomycetous fungus from a freshwater habitat in China - Su-Qin Peng; Yu-Lin Liu; Jun-En Huang; Xiao-Hong Li; Xin-Yi Yan; Hai-Yan Song; Yang Gao; Zhi-Jun Zhai; Yuan-Qiu Liu; Dian-Ming Hu (Archives of Microbiology, 2022)

Qipengyuania thermophila sp. nov., isolated from a Chinese hot spring - Zi-Yu Zhao; Ting-Ting Xia; Jian-Yu Jiao; Lan Liu; Qing-Yang Su; Meng-Meng Li; Ai-Ping Lv; Yu-Ting Ouyang; Wen-Jun Li; Hong Ming (Archives of Microbiology, 2022)

Electrical resistivity imaging in Shibaozhai area using magnetotelluric sounding: Enlightenment of hydrocarbon reservoirs on the eastern edge of the Sichuan Basin - Shu-Ming Wang; Qing-Yun Di; Gui-An Zou; Xiao-Lu Su; Cai Qian; Ruo Wang; De-Shan Li (Applied Geophysics, 2022)

Flavonoid glycosides from the nectar of Camellia reticulata Lindl. - Xin-Lan Chen; Xing-Rong Peng; Xue-Yang Gong; Yi-Qiu Liu; Zhuo Qing; Xiao-Xiao Ren; Rui Su; Li-Ming Fang; Ming-Hua Qiu; Kun Dong (Natural Product Research, 2022)

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

Near-epicenter weather conditions several hours before strong earthquakes (Ms ≥ 6) - Tao Chen; Lei Li; Xiao-Xin Zhang; Qi-Ming Ma; Wen Li; Shuo Ti; Han Wu; Ren-Kang Li; Jing Luo; Jian-Feng Su (Natural Hazards, 2022)

A contribution to knowledge of Gyroporus (Gyroporaceae, Boletales) in China: three new taxa, two previous species, and one ambiguous taxon - Hui-Jing Xie; Li-Ping Tang; Man Mu; Yu-Guang Fan; Shuai Jiang; Ming-Sheng Su; Zhi-Qun Liang; Nian-Kai Zeng (Mycological Progress, 2022)

Characterization of the novel hybrid cultivar E25 of Saccharina japonica in the northern farming region of China - Li Su; Ti Feng Shan; Jing Li; Su Qin Gao; Shao Jun Pang; Xiao Fei Leng; Yan Zhang; Ming Fu Zhang; Hong Tao Gao (Journal of Applied Phycology, 2021)

Inhibition of Maternal c-Src Ameliorates the Male Offspring Hypertension by Suppressing Inflammation and Neurotransmitters in the Paraventricular Nucleus - Qing Su; Xiao-Jing Yu; Qing Yang; Xiao-Min Wang; Wen-Jie Xia; Hong-Bao Li; Kai-Li Liu; Qiu-Yue Yi; Yu-Ming Kang (Cardiovascular Toxicology, 2021)

Supply‐controlled calcium carbonate dissolution decouples the seasonal dissolved oxygen and pH minima in Chesapeake Bay - Jianzhong Su; Wei‐Jun Cai; Jeremy M. Testa; Jean R. Brodeur; Baoshan Chen; K. Michael Scaboo; Ming Li; Chunqi Shen; Margaret Dolan; Yuan‐Yuan Xu; Yafeng Zhang; Najid Hussain (Limnology and Oceanography, 2021)
Acidification can present a stress on organisms and habitats in estuaries in addition to hypoxia. Although oxygen and pH decreases are generally coupled due to aerobic respiration, pH dynamics may be more complex given the multiple modes of buffering in the carbonate system. We studied the seasonal cycle of dissolved oxygen (DO), pH, dissolved inorganic carbon, total alkalinity, and calcium ion (Ca 2+ ) along the main channel of Chesapeake Bay from May to October in 2016. Contrary to the expected co‐occurrence of seasonal DO and pH declines in subsurface water, we found that the pH decline ended in June while the DO decline continued until August in mid‐Chesapeake Bay. We discovered that aerobic respiration was strong from May to August, but carbonate dissolution was minor in May and June and became substantial in August, which buffered further pH declines and caused the seasonal DO and pH minima mismatch. The rate of calcium carbonate (CaCO 3 ) dissolution was not primarily controlled by the saturation state in bottom water, but was instead likely controlled by the supply of CaCO 3 particles. The seasonal variability of Ca 2+ addition in the mid‐bay was connected to Ca 2+ removal in the upper bay, and the timing of high carbonate dissolution coincided with peak seasonal biomass of upper Bay submerged aquatic vegetation. This study suggests a mechanism for a novel decoupling of DO and pH in estuarine waters associated with CaCO 3 , but future studies are needed to fully investigate the seasonality of physical transport and cycling of CaCO 3 .

Genome-wide identification of auxin response factor (ARF) family in kiwifruit (Actinidia chinensis) and analysis of their inducible involvements in abiotic stresses - Liyan Su; Ming Xu; Jiudong Zhang; Yihang Wang; Yushan Lei; Qiang Li (Physiology and Molecular Biology of Plants, 2021)

Molecular Imaging for Radiolabeling a PSMA-Targeted Long Circulating Peptide as a Theranostic Agent in Mice Bearing a Human Prostate Tumor - Ming-Hsin Li; Sheng-Nan Lo; Ming-Wei Chen; Wei-Lin Lo; Yuan-Ruei Huang; Shih-Ying Lee; Su-Jung Chen; Shih-Wei Lo; Shih-Ming Wang; Chih-Hsien Chang (Journal of Medical and Biological Engineering, 2021)

Proton Pump Inhibitor Exposure and Acute Myocardial Infarction Risk: A Nested Cohort Study - Hsiang-Jung Tseng; Chih-Ming Cheng; Shih-Jen Tsai; Wei-Chen Lin; Ya-Mei Bai; Chia-Fen Tsai; Tung-Ping Su; Cheng-Ta Li; Tzeng-Ji Chen; Mu-Hong Chen (Cardiovascular Toxicology, 2021)

Study on Microwave Heating Order and Electromagnetic Characteristics of Copper and Gold Ores - Feng Lin; Xia-Ting Feng; Gao-Ming Lu; Xiang-Xin Su; Shi-Ping Li; Jiu-yu Zhang (Rock Mechanics and Rock Engineering, 2021)

Targeted deletion of HAI-1 increases prostasin proteolysis but decreases matriptase proteolysis in human keratinocytes - Dajun D. Lu; Yayun Gu; Sheng-Wen A. Li; Robert J. Barndt; Shih-Ming Huang; Jehng-Kang Wang; Hui Chen Su; Michael D. Johnson; Chen-Yong Lin (Human Cell, 2021)

The highly conserved rps12 gene in ferns provides strong evidence for decreased substitution rates in the inverted repeat region - Jingyao Ping; Aimin Li; Peipei Feng; Ming Zhu; Yingjuan Su; Ting Wang (Plant Systematics and Evolution, 2021)

Correction to: Central Blockade of E-Prostanoid 3 Receptor Ameliorated Hypertension Partially by Attenuating Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus of Spontaneously Hypertensive Rats - Fang-Fang Wang; Juan Bai; Xiao-Jing Yu; Xiao-Lian Shi; Jin-Jun Liu; Kai-Li Liu; Li-Yan Fu; Qing Su; Hong-Bao Li; Kai B. Kang; Qiu-Yue Yi; Shu-Qiu Wang; et al. (Cardiovascular Toxicology, 2021)

Central Blockade of E-Prostanoid 3 Receptor Ameliorated Hypertension Partially by Attenuating Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus of Spontaneously Hypertensive Rats - Fang-Fang Wang; Juan Ba; Xiao-Jing Yu; Xiao-Lian Shi; Jin-Jun Liu; Kai-Li Liu; Li-Yan Fu; Qing Su; Hong-Bao Li; Kai B. Kang; Qiu-Yue Yi; Shu-Qiu Wang; et al. (Cardiovascular Toxicology, 2021)

Simultaneous detection of multiple bacterial and viral aquatic pathogens using a fluorogenic loop‐mediated isothermal amplification‐based dual‐sample microfluidic chip - Qian‐Jin Zhou; Jian‐Fei Lu; Xiu‐Rong Su; Jing‐Lei Jin; Shang‐Yang Li; Yan Zhou; Lei Wang; Xin‐Bin Shao; Yao‐Hua Wang; Mao‐Cang Yan; Ming‐Yun Li; Jiong Chen (Journal of Fish Diseases, 2021)
Rapid and user‐friendly diagnostic tests are necessary for early diagnosis and immediate detection of diseases, particularly for on‐site screening of pathogenic microorganisms in aquaculture. In this study, we developed a dual‐sample microfluidic chip integrated with a real‐time fluorogenic loop‐mediated isothermal amplification assay (dual‐sample on‐chip LAMP) to simultaneously detect 10 pathogenic microorganisms, that is Aeromonas hydrophila , Edwardsiella tarda , Vibrio harveyi , V. alginolyticus , V. anguillarum , V. parahaemolyticus , V. vulnificus , infectious hypodermal and haematopoietic necrosis virus, infectious spleen and kidney necrosis virus, and white spot syndrome virus. This on‐chip LAMP provided a nearly automated protocol that can analyse two samples simultaneously, and the tests achieved limits of detection (LOD) ranging from 10 0 to 10 –1 pg/μl for genomic DNA of tested bacteria and 10 –4 to 10 –5 pg/μl for recombinant plasmid DNA of tested viruses, with run times averaging less than 30 min. The coefficient of variation for the time‐to‐positive value was less than 10%, reflecting a robust reproducibility. The clinical sensitivity and specificity were 93.52% and 85.53%, respectively, compared to conventional microbiological or clinical methods. The on‐chip LAMP assay provides an effective dual‐sample and multiple pathogen analysis, and thus would be applicable to on‐site detection and routine monitoring of multiple pathogens in aquaculture.

Spatial distribution and environmental significance of phytoliths in the surface soil of the Xilingol Grassland in Inner Mongolia, China - Chong-Xiao Sun; Hua Su; Cai-Qing Guo; Zhi-Wei Liu; Ya-Meng Li; Feng Qin; Hai-Ming Liu (Palaeobiodiversity and Palaeoenvironments, 2021)

Dietary lipid concentrations influence growth, body composition, morphology of the liver and mid-intestine, and antioxidant status of marbled eel (Anguilla marmorata) - Shi-Jun Chen; Peng Liu; You-Ming Jia; Hong-Ping Liao; Shao-Xuan Zhu; Li-Liu Zhou; Xue-Ming Dan; Li Liu; Jia-Hao Li; Su-Bi Zheng; Jun-Jiang Yang; Lian Gan (Aquaculture International, 2020)

LMDS-1, a potential TrkB receptor agonist provides a safe and neurotrophic effect for early-phase Alzheimer’s disease - Chia-Hao Fan; Chia-Wei Lin; Hei-Jen Huang; Guey-Jen Lee-Chen; Ying-Chieh Sun; Wenwei Lin; Chiung-Mei Chen; Kuo-Hsuan Chang; Ming-Tsan Su; Hsiu Mei Hsieh-Li (Psychopharmacology, 2020)

Hydrogeochemical and isotopic characteristics of groundwater in Xinchang preselected site and their implications - Zhichao Zhou; Ju Wang; Rui Su; Yonghai Guo; Jingbo Zhao; Ming Zhang; Ruili Ji; Yanan Li; Jiebiao Li (Environmental Science and Pollution Research, 2020)

Surface heterogeneity mediated transport of hydrochar nanoparticles in heterogeneous porous media - Jing Yang; Ming Chen; Han Yang; Nan Xu; Gang Feng; Zuling Li; Chunming Su; Dengjun Wang (Environmental Science and Pollution Research, 2020)

Structural features of an acidic polysaccharide with the potential of promoting osteoblast differentiation from Lycium ruthenicum Murr. - Shu-Qi Wang; Bing Liu; Su Liu; Song-Zi Xie; Li-Hua Pan; Xue-Qiang Zha; Qiang-Ming Li; Jian-Ping Luo (Natural Product Research, 2020)

TMEM88 modulates the secretion of inflammatory factors by regulating YAP signaling pathway in alcoholic liver disease - Liang-yun Li; Chen-chen Yang; Su-wen Li; Yu-min Liu; Hao-dong Li; Shuang Hu; Hong Zhou; Jin-liang Wang; Hang Shen; Xiao-ming Meng; Jun Li; Tao Xu (Inflammation Research, 2020)

Immunomagnetic separation-based nanogold enhanced surface plasmon resonance and colloidal gold test strips for rapid detection of Vibrio parahaemolyticus - Jun Zhou; Chundan Zhang; Xuan Zhang; Chenyang Lu; Tinghong Ming; Ye Li; Xiurong Su (Archives of Microbiology, 2020)

Combined effect of polymorphisms of MTHFR and MTR and arsenic methylation capacity on developmental delay in preschool children in Taiwan - Yu-Mei Hsueh; Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Horng-Sheng Shiue; Ssu-Ning Chien; Chih-Ying Lee; Ming-I. Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2020)

A DTW distance-based seismic waveform clustering method for layers of varying thickness - Zhong Hong; Kun-Hong Li; Ming-Jun Su; Guang-Min Hu; Jun Yang; Gai Gao; Bin Hao (Applied Geophysics, 2020)

Physiological and proteomic responses of mangrove plant Avicennia marina seedlings to simulated periodical inundation - Huan Li; Zan Li; Zhi-Jun Shen; Mei-Rong Luo; Yi-Ling Liu; Ming-Yue Wei; Wen-Hua Wang; Ying-Ying Qin; Chang-Hao Gao; Ke-Ke Li; Qian-Su Ding; Shan Zhang; et al. (Plant and Soil, 2020)

The BIG gene controls size of shoot apical meristems in Arabidopsis thaliana - Wen Jie Zhang; Li Ming Zhai; Hai Xia Yu; Jing Peng; Shan Shan Wang; Xian Sheng Zhang; Ying Hua Su; Li Ping Tang (Plant Cell Reports, 2020)

Thioredoxin-Interacting Protein (TXNIP) Regulates Parkin/PINK1-mediated Mitophagy in Dopaminergic Neurons Under High-glucose Conditions: Implications for Molecular Links Between Parkinson’s Disease and Diabetes - Cun-Jin Su; Zhu Shen; Ru-Xiao Cui; Ya Huang; De-Lai Xu; Feng-Lun Zhao; Jie Pan; Ai-Ming Shi; Tong Liu; Yun-Li Yu (Neuroscience Bulletin, 2020)

Blockade of c-Src Within the Paraventricular Nucleus Attenuates Inflammatory Cytokines and Oxidative Stress in the Mechanism of the TLR4 Signal Pathway in Salt-Induced Hypertension - Qing Yang; Xiao-Jing Yu; Qing Su; Qiu-Yue Yi; Xin-Ai Song; Xiao-Lian Shi; Hong-Bao Li; Jie Qi; Guo-Qing Zhu; Yu-Ming Kang (Neuroscience Bulletin, 2020)

NMR-based metabolomics reveals the metabolite profiles of Vibrio parahaemolyticus under blood agar stimulation - Jun Zhou; Chundan Zhang; Jiaojiao Han; Chenyang Lu; Ye Li; Tinghong Ming; Xiurong Su (Archives of Microbiology, 2020)

Genome-wide identification and expression analysis of the StSWEET family genes in potato (Solanum tuberosum L.) - Ming Li; Haijuan Xie; Miaomiao He; Wang Su; Yongzhi Yang; Jian Wang; Guangji Ye; Yun Zhou (Genes & Genomics, 2020)

Spatial distribution characteristics of bacterial community structure and gene abundance in sediments of the Bohai Sea - Quanrui Chen; Jingfeng Fan; Jie Su; Hongxia Ming; Zhihao Sun; Mengfei Li; Xiaohui Zhao; Yantao Wang; Yingxue Zhang; Huizhen Zhang; Yuan Jin; Xiaowan Ma; et al. (Acta Oceanologica Sinica, 2020)

Association of plasma folate, vitamin B12 levels, and arsenic methylation capacity with developmental delay in preschool children in Taiwan - Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Pui-Lam Ao; Horng-Sheng Shiue; Shiau-Rung Huang; Chien-Tien Su; Ming-I Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2019)

Chronic low dose of AM404 ameliorates the cognitive impairment and pathological features in hyperglycemic 3xTg-AD mice - Hei-Jen Huang; Shu-Ling Chen; Hsin-Yu Huang; Ying-Chieh Sun; Guan-Chiun Lee; Guey-Jen Lee-Chen; Hsiu Mei Hsieh-Li; Ming-Tsan Su (Psychopharmacology, 2019)

Improving seed germination and oil contents by regulating the GDSL transcriptional level in Brassica napus - Li-Na Ding; Xiao-Juan Guo; Ming Li; Zheng-Li Fu; Su-Zhen Yan; Ke-Ming Zhu; Zheng Wang; Xiao-Li Tan (Plant Cell Reports, 2019)

Chronic Intracerebroventricular Infusion of Metformin Inhibits Salt-Sensitive Hypertension via Attenuation of Oxidative Stress and Neurohormonal Excitation in Rat Paraventricular Nucleus - Xiao-Jing Yu; Ya-Nan Zhao; Yi-Kang Hou; Hong-Bao Li; Wen-Jie Xia; Hong-Li Gao; Kai-Li Liu; Qing Su; Hui-Yu Yang; Bin Liang; Wen-Sheng Chen; Wei Cui; et al. (Neuroscience Bulletin, 2019)

Blockade of Endogenous Angiotensin-(1–7) in Hypothalamic Paraventricular Nucleus Attenuates High Salt-Induced Sympathoexcitation and Hypertension - Xiao-Jing Yu; Yu-Wang Miao; Hong-Bao Li; Qing Su; Kai-Li Liu; Li-Yan Fu; Yi-Kang Hou; Xiao-Lian Shi; Ying Li; Jian-Jun Mu; Wen-Sheng Chen; Wei Cui; et al. (Neuroscience Bulletin, 2019)

Rutin protects against lipopolysaccharide-induced mastitis by inhibiting the activation of the NF-κB signaling pathway and attenuating endoplasmic reticulum stress - Siyi Su; Xiaoyu Li; Siting Li; Pengfei Ming; Yingying Huang; Yanli Dong; Hongyan Ding; Shibin Feng; Jinchun Li; Xichun Wang; Yu Li; Jinjie Wu (Inflammopharmacology, 2019)

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

Determination of dietary nitrite in patients with esophageal pre-cancerous lesion and normal people: a duplicate diet study - Ting Zhang; Da Pan; Ming Su; Ling-Meng Fu; Cai-Yun Miao; Qing-Yang Yan; Jing Wang; Li-Gang Yang; Shao-Kang Wang; Gui-Ju Sun (Food Additives & Contaminants: Part A, 2018)

Genetic diversity and large-scale connectivity of the scleractinian coral Porites lutea in the South China Sea - Wen Huang; Ming Li; Kefu Yu; Yinghui Wang; Jingjing Li; Jiayuan Liang; Yanqiu Luo; Xueyong Huang; Zhenjun Qin; Guanghua Wang; Hongfei Su; Fen Wei (Coral Reefs, 2018)

Associations of HSP90AA2 gene polymorphisms with disease susceptibility, glucocorticoids efficacy and health-related quality of life in Chinese systemic lupus erythematosus patients - Man Zhang; Su-Su Li; Qiao-Mei Xie; Jian-Hua Xu; Xiu-Xiu Sun; Fa-Ming Pan; Sheng-Qian Xu; Sheng-Xiu Liu; Jin-Hui Tao; Shuang Liu; Jing Cai; Pei-Ling Chen; et al. (Genes & Genomics, 2018)

Dynamic behaviour of weathered red mudstone in Sichuan (China) under triaxial cyclic loading - Chong-lei Zhang; Guan-lu Jiang; Li-jun Su; Wei-ming Liu (Journal of Mountain Science, 2018)

An improved grey wolf optimizer algorithm for the inversion of geoelectrical data - Si-Yu Li; Shu-Ming Wang; Peng-Fei Wang; Xiao-Lu Su; Xin-Song Zhang; Zhi-Hui Dong (Acta Geophysica, 2018)

Effect of dry density on the liquefaction behaviour of Quaternary silt - Chong-lei Zhang; Guan-lu Jiang; Li-jun Su; Wei-ming Liu; Gong-dan Zhou (Journal of Mountain Science, 2018)

Re–Os dating of molybdenite and in-situ Pb isotopes of sulfides from the Lamo Zn–Cu deposit in the Dachang tin-polymetallic ore field, Guangxi, China - Hai Zhao; Wenchao Su; Peng Xie; Nengping Shen; Jiali Cai; Ming Luo; Jie Li; Zhian Bao (Acta Geochimica, 2018)

Nutrient Decomposition Rate and Sugarcane Yield as Influenced by Mung Bean Intercropping and Crop Residue Recycling - Tie-Guang He; Li-Rong Su; Yang-Rui Li; Tian-Ming Su; Fang Qin; Qin Li (Sugar Tech, 2018)

Different Hippocampus Functional Connectivity Patterns in Healthy Young Adults with Mutations of APP/Presenilin-1/2 and APOEε4 - Li Juan Zheng; Yun Yan Su; Yun Fei Wang; U. Joseph Schoepf; Akos Varga-Szemes; Jonathan Pannell; Xue Liang; Gang Zheng; Guang Ming Lu; Gui Fen Yang; Long Jiang Zhang (Molecular Neurobiology, 2018)

PKM2 knockdown influences SREBP activation and lipid synthesis in bovine mammary-gland epithelial MAC-T cells - Bing-Qian Su; Ying-Qian Han; Shuang-Shuang Fan; Sheng-Li Ming; Bo Wan; Wei-Fei Lu; Bei-Bei Chu; Guo-Yu Yang; Jiang Wang (Biotechnology Letters, 2018)

Detrital provenance, depositional environment, and palaeogeographic implications of Lower Triassic marine sediments in central Tibet - Chao-ming Xie; Cai Li; Yun-sheng Ren; Ming Wang; Li Su (International Geology Review, 2018)

Analysis of future drought characteristics in China using the regional climate model CCLM - Jinlong Huang; Jianqing Zhai; Tong Jiang; Yanjun Wang; Xiucang Li; Run Wang; Ming Xiong; Buda Su; Thomas Fischer (Climate Dynamics, 2018)

Ordovician sedimentation and bimodal volcanism in the Southern Qiangtang terrane of northern Tibet: Implications for the evolution of the northern Gondwana margin - Chao-ming Xie; Cai Li; Jian-jun Fan; Li Su (International Geology Review, 2017)

Anti-hepatocellular carcinoma activity of tormentic acid derived from suspension cells of Eriobotrya japonica (Thunb.) Lindl. - Hui-Hua Li; Ming-Hua Su; De-Heng Yao; Bi-Yu Zeng; Qiang Chang; Wei Wang; Jian Xu (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Altered white matter microstructure identified with tract-based spatial statistics in irritable bowel syndrome: a diffusion tensor imaging study - Jin Fang; Shumei Li; Meng Li; Queenie Chan; Xiaofen Ma; Huanhuan Su; Tianyue Wang; Wenfeng Zhan; Jianhao Yan; Ming Xu; Yaxi Zhang; Luxian Zeng; et al. (Brain Imaging and Behavior, 2017)

Lower functional connectivity of default mode network in cognitively normal young adults with mutation of APP, presenilins and APOE ε4 - Yun Yan Su; Xiao Dong Zhang; U. Joseph Schoepf; Akos Varga-Szemes; Andrew Stubenrauch; Xue Liang; Li Juan Zheng; Gang Zheng; Xiang Kong; Qiang Xu; Shou Ju Wang; Rong Feng Qi; et al. (Brain Imaging and Behavior, 2017)

Spatial Abundance, Diversity, and Activity of Ammonia-Oxidizing Bacteria in Coastal Sediments of the Liaohe Estuary - Yongkai Chang; Jingfeng Fan; Jie Su; Hongxia Ming; Wen Zhao; Yan Shi; Fengyun Ji; Limei Guo; Shuaijun Zan; Bochao Li; Hao Guo; Daoming Guan (Current Microbiology, 2017)

Overexpression of the ascorbate peroxidase gene from eggplant and sponge gourd enhances flood tolerance in transgenic Arabidopsis - Chih-Ming Chiang; Chiu-Chen Chen; Shi-Peng Chen; Kuan-Hung Lin; Li-Ru Chen; Yu-Huei Su; His-Cheng Yen (Journal of Plant Research, 2017)

Regional selection of the brain size regulating gene CASC5 provides new insight into human brain evolution - Lei Shi; Enzhi Hu; Zhenbo Wang; Jiewei Liu; Jin Li; Ming Li; Hua Chen; Chunshui Yu; Tianzi Jiang; Bing Su (Human Genetics, 2017)

Population structure and diversity of citrus tristeza virus (CTV) isolates in Hunan province, China - Cui Xiao; Run-Xian Yao; Fang Li; Su-Ming Dai; Grazia Licciardello; Antonino Catara; Alessandra Gentile; Zi-Niu Deng (Archives of Virology, 2017)

Gastroprotective effect of palmatine against acetic acid-induced gastric ulcers in rats - Ling Wang; Xue Wang; Su-Li Zhang; Xiao-Ming Zhu; Yan-Qi Liu; Zi-Jing Song; Wen-Juan Du; Jun Ji; Cheng-Long Cui; Xin He; Chun-Feng Zhang; Chang-Run Guo; et al. (Journal of Natural Medicines, 2017)

A high throughput method for rapid screening of chitosanase-producing fungal strain under acidic conditions - Su Ding; Gui-Guang Chen; Zhi-Qun Liang; Wei Zeng; Mu-Ming Cao; Guo-Pin Chen; Shu-Yu Xie; Wei Li (World Journal of Microbiology and Biotechnology, 2016)

Redistribution of Cav2.1 channels and calcium ions in nerve terminals following end-to-side neurorrhaphy: ionic imaging analysis by TOF–SIMS - Chiung-Hui Liu; Hung-Ming Chang; To-Jung Tseng; Chyn-Tair Lan; Li-You Chen; Su-Chung Youn; Jian-Jr Lee; Fu-Der Mai; Jui-Feng Chou; Wen-Chieh Liao (Histochemistry and Cell Biology, 2016)

Distinct effect of pH on N uptake and assimilation in two conifer species - Sen Meng; Chun-xia Zhang; Li Su; Yi-Ming Li; Yang Cao; Zhong Zhao (Trees, 2016)

Meta-Analysis of the COMT Val158Met Polymorphism in Major Depressive Disorder: Effect of Ethnicity - Maiqiu Wang; Yunlong Ma; Wenji Yuan; Kunkai Su; Ming D. Li (Journal of Neuroimmune Pharmacology, 2016)

Paraventricular Nucleus Infusion of Epigallocatechin-3-O-Gallate Improves Renovascular Hypertension - Qiu-Yue Yi; Jie Qi; Xiao-Jing Yu; Hong-Bao Li; Yan Zhang; Qing Su; Tao Shi; Dong-Mei Zhang; Jing Guo; Zhi-Peng Feng; Mo-Lin Wang; Guo-Qing Zhu; et al. (Cardiovascular Toxicology, 2016)

Salusin β Within the Nucleus Tractus Solitarii Suppresses Blood Pressure Via Inhibiting the Activities of Presympathetic Neurons in the Rostral Ventrolateral Medulla in Spontaneously Hypertensive Rats - Hong-Bao Li; Yan Lu; Jin-Jun Liu; Yu-Wang Miao; Tian-Zhen Zheng; Qing Su; Jie Qi; Hong Tan; Zu-Yi Yuan; Guo-Qing Zhu; Yu-Ming Kang (Cardiovascular Toxicology, 2016)

Myricetin protects against diet-induced obesity and ameliorates oxidative stress in C57BL/6 mice - Hong-ming Su; Li-na Feng; Xiao-dong Zheng; Wei Chen (Journal of Zhejiang University-SCIENCE B, 2016)

Geo-engineered buffer capacity of two-layered absorbing system under the impact of rock avalanches based on Discrete Element Method - Yu-zhang Bi; Si-ming He; Xin-po Li; Yong Wu; Qiang Xu; Chao-jun Ouyang; Li-Jun Su; Hao Wang (Journal of Mountain Science, 2016)

Adaptive evolution of interleukin-3 (IL3), a gene associated with brain volume variation in general human populations - Ming Li; Liang Huang; Kaiqin Li; Yongxia Huo; Chunhui Chen; Jinkai Wang; Jiewei Liu; Zhenwu Luo; Chuansheng Chen; Qi Dong; Yong-gang Yao; Bing Su; et al. (Human Genetics, 2016)

The impacts of migrant workers consumption on energy use and CO2 emissions in China - Jing-Li Fan; Hua Liao; Bao-Jun Tang; Su-Yan Pan; Hao Yu; Yi-Ming Wei (Natural Hazards, 2016)

The microRNA167 controls somatic embryogenesis in Arabidopsis through regulating its target genes ARF6 and ARF8 - Ying Hua Su; Yu Bo Liu; Chao Zhou; Xiao Ming Li; Xian Sheng Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

NMDAR-Mediated Hippocampal Neuronal Death is Exacerbated by Activities of ASIC1a - Su Gao; Yang Yu; Zhi-Yuan Ma; Hui Sun; Yong-Li Zhang; Xing-Tao Wang; Chaoyun Wang; Wei-Ming Fan; Qing-Yin Zheng; Chun-Lei Ma (Neurotoxicity Research, 2015)

Two genes conferring resistance to Pythium stalk rot in maize inbred line Qi319 - Feng-Jing Song; Ming-Gang Xiao; Can-Xing Duan; Hong-Jie Li; Zhen-Dong Zhu; Bao-Tao Liu; Su-Li Sun; Xiao-Fei Wu; Xiao-Ming Wang (Molecular Genetics and Genomics, 2015)

TM-1-1DP exerts protective effect against myocardial ischemia reperfusion injury via AKT-eNOS pathway - Hui-Chun Ku; Shih-Yi Lee; Chi-Hsuan Chen; Yao-Hsing Wang; Chin-Ting Lin; Shoei-Sheng Lee; Ting-Hsuan Li; Ming-Jai Su (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Identification and localized expression of putative K+/H+ antiporter genes in Arabidopsis - Lei Han; Jun Lin Li; Li Wang; Wei Ming Shi; Yan Hua Su (Acta Physiologiae Plantarum, 2015)

Regional integrated environmental modeling system: development and application - Shuyu Wang; Congbin Fu; Helin Wei; Yun Qian; Zhe Xiong; Jinming Feng; Deming Zhao; Li Dan; Zhiwei Han; Bingkai Su; Ming Zhao; Yaocun Zhang; et al. (Climatic Change, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Early-life sleep deprivation persistently depresses melatonin production and bio-energetics of the pineal gland: potential implications for the development of metabolic deficiency - Li-You Chen; Cheng Tiong; Chung-Hung Tsai; Wen-Chieh Liao; Shun-Fa Yang; Su-Chung Youn; Fu-Der Mai; Hung-Ming Chang (Brain Structure and Function, 2015)

Upregulation of HIF-1α Via Activation of ERK and PI3K Pathway Mediated Protective Response to Microwave-Induced Mitochondrial Injury in Neuron-Like Cells - Li Zhao; Yue-Feng Yang; Ya-Bing Gao; Shui-Ming Wang; Li-Feng Wang; Hong-Yan Zuo; Ji Dong; Xin-Ping Xu; Zhen-Tao Su; Hong-Mei Zhou; Ling-Ling Zhu; Rui-Yun Peng (Molecular Neurobiology, 2014)

Identification of a potential novel type of influenza virus in Bovine in China - Wen-Ming Jiang; Su-Chun Wang; Cheng Peng; Jian-Min Yu; Qing-Ye Zhuang; Guang-Yu Hou; Shuo Liu; Jin-Ping Li; Ji-Ming Chen (Virus Genes, 2014)

A convenient four-component one-pot synthesis of 2-amino-1,3,4-thiadiazoles in water - Peng Liu; Ao-Ze Su; Yuan-Qiang Wang; Ze-Mei Ge; Tie-Ming Cheng; Run-Tao Li (Molecular Diversity, 2014)

Effect of NeuroD Gene Silencing on the Migration and Invasion of Human Pancreatic Cancer Cells PANC-1 - Yang Wang; Dong Wei Su; Li Gao; Gui Ling Ding; Can Rong Ni; Ming Hua Zhu (Cell Biochemistry and Biophysics, 2014)

Engrailed-2 is down-regulated but also ectopically expressed in clear cell renal cell carcinoma - Cai-yong Lai; Bin Pan; Yun Luo; Wei-bo Liang; Jie Chen; Dong-ming Ye; Ji-Nan Guo; Li Li; Ze-xuan Su (Molecular Biology Reports, 2014)

Association of genetic variants in estrogen receptor α with HCV infection susceptibility and viral clearance in a high-risk Chinese population - Shaidi Tang; Ming Yue; Jiajia Wang; Jing Su; Rongbin Yu; Donghui Zhou; Ke Xu; Li Cai; Yun Zhang; Jie Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Identification of BACH2 as a susceptibility gene for Graves’ disease in the Chinese Han population based on a three-stage genome-wide association study - Wei Liu; Hai-Ning Wang; Zhao-Hui Gu; Shao-Ying Yang; Xiao-Ping Ye; Chun-Ming Pan; Shuang-Xia Zhao; Li-Qiong Xue; Hui-Jun Xie; Sha-Sha Yu; Cui-Cui Guo; Wen-Hua Du; et al. (Human Genetics, 2014)

Ecological suitability assessment and introduction experiment on Rosa damascena trigintipetala in Sichuan Province, China - Xiao-lan Wang; Chun-jiang Su; Li Peng; Hai-e Wang; Hai-ming Wang; Wei Liu; Ping Li; Yan Fang (Journal of Mountain Science, 2014)

CRP Gene polymorphism contributes genetic susceptibility to dyslipidemia in Han Chinese population - Wenbin Wei; Song Yang; Yingru Qiu; Hairu Wang; Xianghai Zhao; Yanping Zhao; Yun Li; Ming Wu; Yanchun Chen; Wen Wang; Xiaoming Shi; Sijun Liu; et al. (Molecular Biology Reports, 2014)

Depositional characteristics and spatial distribution of deep-water sedimentary systems on the northwestern middle-lower slope of the Northwest Sub-Basin, South China Sea - Hui Chen; Xinong Xie; David Van Rooij; Thomas Vandorpe; Li Huang; Laiyuan Guo; Ming Su (Marine Geophysical Research, 2013)

Epidemiology and full genome sequence analysis of H1N1pdm09 from Northeast China - Xiaoyan Li; Mei Kong; Jinying Chen; Xu Su; Ming Zou; Liru Guo; Lin Li; Jianqing Ding (Virus Genes, 2013)

Reduction of connexin43 in human endothelial progenitor cells impairs the angiogenic potential - Hsueh-Hsiao Wang; Cheng-Huang Su; Yih-Jer Wu; Jiun-Yi Li; Ya-Ming Tseng; Yi-Chun Lin; Chin-Ling Hsieh; Cheng-Ho Tsai; Hung-I Yeh (Angiogenesis, 2013)

Acid loading stimulates rat glomerular mesangial cells proliferation through Na+–H+ exchanger isoform 1 (NHE1)-dependent pathway - Kun Li; Wei Su; Man Li; Chang-jie Chen; Yong-yu Li; Lin-yun Lai; Ming-min Zhang; Shao-jun Liu; Jakub Fichna; Ai Peng; Chuan-ming Hao; Yong Gu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Catalog of Erycina pusilla miRNA and categorization of reproductive phase-related miRNAs and their target gene families - Choun-Sea Lin; Jeremy J. W. Chen; Yao-Ting Huang; Chen-Tran Hsu; Hsiang-Chia Lu; Ming-Lun Chou; Li-Chi Chen; Chia-I Ou; Der-Chih Liao; Ysuan-Yu Yeh; Song-Bing Chang; Su-Chen Shen; et al. (Plant Molecular Biology, 2013)

Risk factors for primary lung cancer among never smokers by gender in a matched case–control study - Yen-Li Lo; Chin-Fu Hsiao; Gee-Chen Chang; Ying-Huang Tsai; Ming-Shyan Huang; Wu-Chou Su; Yuh-Min Chen; Che-Wei Hsin; Chin-Hao Chang; Pan-Chyr Yang; Chien-Jen Chen; Chao A. Hsiung (Cancer Causes & Control, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

The active alkaloids of Gelsemium elegans Benth. are potent anxiolytics - Ming Liu; Hui-Hui Huang; Jian Yang; Yan-Ping Su; Hong-Wei Lin; Li-Qing Lin; Wei-Jian Liao; Chang-Xi Yu (Psychopharmacology, 2013)

Molecular epidemiology of PRRSV from China’s Guangxi Province between 2007 and 2009 - Hong-Yun Zhang; Jing-Jing Liang; Xian-Ming Meng; Hui Li; Jian Yang; Li-Juan Su; Hong-Pu Zhang; Lin-Juan Xie; Xiao-Xia He; Yan-Sheng Li; Shan Yin; Xiao-Quan Li; et al. (Virus Genes, 2013)

Tectonic mechanism of the Suining (Ms5.0) earthquake, center of Sichuan Basin, China - Rong-jun Zhou; Yong Li; Laurence Svirchev; Yong-jiu Zhang; Deng-fa He; Yu-lin He; Pei-lin Zhao; Zan-jun Wang; Feng Long; Jin-rong Su; Shi-yuan Wang; Ming-jian Liang; et al. (Journal of Mountain Science, 2013)

The Effect of Osteochondral Regeneration Using Polymer Constructs and Continuous Passive Motion Therapy in the Lower Weight-Bearing Zone of Femoral Trocheal Groove in Rabbits - Nai-Jen Chang; Chih-Chan Lin; Chien-Feng Li; Kai Su; Ming-Long Yeh (Annals of Biomedical Engineering, 2013)

STAT1 activation by venous malformations mutant Tie2-R849W antagonizes VEGF-A-mediated angiogenic response partly via reduced bFGF production - Yi-Hsien Huang; Ming-Ping Wu; Shin-Chen Pan; Wu-Chou Su; Yi-Wen Chen; Li-Wha Wu (Angiogenesis, 2013)

Effect of Long-Term Vinasse Application on Physico-chemical Properties of Sugarcane Field Soils - Ze-Pu Jiang; Yang-Rui Li; Guang-Po Wei; Qing Liao; Tian-Ming Su; Yan-Cheng Meng; Hai-Ying Zhang; Chang-Yan Lu (Sugar Tech, 2012)

Macronutrients Absorption and Surface Runoff Losses Under Different Fertilizer Treatments in Sugarcane Field - Tian-Ming Su; Yang-Rui Li; Guang-Po Wei; Ze-Pu Jiang; Qing Liao; Shu-Biao Zhu (Sugar Tech, 2012)

Genome-wide Identification and Characterization of a Dehydrin Gene Family in Poplar (Populus trichocarpa) - Chang-Cai Liu; Chun-Ming Li; Bao-Guang Liu; Su-Jie Ge; Xiu-Mei Dong; Wei Li; Hang-Yong Zhu; Bai-Chen Wang; Chuan-Ping Yang (Plant Molecular Biology Reporter, 2012)

The evolution and utility of ribosomal ITS sequences in Bambusinae and related species: divergence, pseudogenes, and implications for phylogeny - HUI-XING SONG; SU-PING GAO; MING-YAN JIANG; GUANG-LI LIU; XIAO-FANG YU; QI-BING CHEN (Journal of Genetics, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Down-regulation of β3-integrin inhibits bone metastasis of small cell lung cancer - Na Li; Jian-ping Zhang; Shan Guo; Jie Min; Li–li Liu; Hai-chuan Su; Ying-ming Feng; He-long Zhang (Molecular Biology Reports, 2012)

Intratumoral Heterogeneity Determines Discordant Results of Diagnostic Tests for Human Epidermal Growth Factor Receptor (HER) 2 in Gastric Cancer Specimens - Jiyuan Yang; Hesheng Luo; Yan Li; Junchuan Li; Zhiqiang Cai; Xiaoyan Su; Danqing Dai; Wei Du; Tingxuan Chen; Ming Chen (Cell Biochemistry and Biophysics, 2012)

The effect of down regulation of calcineurin Aα by lentiviral vector-mediated RNAi on the biological behavior of small-cell lung cancer and its bone metastasis - Ning-Qiang Ma; Li-Li Liu; Jie Min; Jun-Wei Wang; Wei-Feng Jiang; Yan Liu; Yan-Guo Feng; Hai-Chuan Su; Ying-Ming Feng; He-Long Zhang (Clinical & Experimental Metastasis, 2011)

Down-Regulation of Tumor-Associated NADH Oxidase, tNOX (ENOX2), Enhances Capsaicin-Induced Inhibition of Gastric Cancer Cell Growth - His-Ming Wang; Show-Mei Chuang; Yu-Ching Su; Yi-Hui Li; Pin Ju Chueh (Cell Biochemistry and Biophysics, 2011)

Induction of DIMBOA accumulation and systemic defense responses as a mechanism of enhanced resistance of mycorrhizal corn (Zea mays L.) to sheath blight - Yuan Yuan Song; Man Cao; Li Jun Xie; Xiao Ting Liang; Ren Sen Zeng; Yi Juan Su; Jing Hua Huang; Rui Long Wang; Shi Ming Luo (Mycorrhiza, 2011)

Accurate assessment of antibiotic susceptibility and screening resistant strains of a bacterial population by linear gradient plate - YuQing Liu; JingRan Li; JiaFa Du; Ming Hu; Hua Bai; Jing Qi; Chao Gao; TianTian Wei; Hong Su; JianLing Jin; PeiJi Gao (Science China Life Sciences, 2011)

Phylogenetic analysis of the E2 gene of classical swine fever virus from the Guangxi Province of southern China - Ting Rong Luo; Su-huan Liao; Xian-shi Wu; Li Feng; Zhao-Xia Yuan; Hui Li; Jing-Jing Liang; Xian-Ming Meng; Hong-Yun Zhang (Virus Genes, 2011)

Trace analysis of persistent toxic substances in the main stream of Jiangsu section of the Yangtze River, China - Huan He; Guan-jiu Hu; Cheng Sun; Su-lan Chen; Ming-na Yang; Juan Li; Yong Zhao; Hui Wang (Environmental Science and Pollution Research, 2011)

Molecular epidemiology of Echovirus 30 in Taiwan, 1988–2008 - Guan-Ming Ke; Kuei-Hsiang Lin; Po-Liang Lu; Yi-Chin Tung; Chu-Feng Wang; Liang-Yin Ke; Min-Sheng Lee; Pei-Chin Lin; Hui-Ju Su; Yi-Ying Lin; Tzu-Ping Huang; Jen-Ren Wang; et al. (Virus Genes, 2011)

Immunomodulative effects of mesenchymal stem cells derived from human embryonic stem cells in vivo and in vitro - Zhou Tan; Zhong-yuan Su; Rong-rong Wu; Bin Gu; Yu-kan Liu; Xiao-li Zhao; Ming Zhang (Journal of Zhejiang University-SCIENCE B, 2011)

Ectopic expression of an EAR motif deletion mutant of SlERF3 enhances tolerance to salt stress and Ralstonia solanacearum in tomato - I-Chun Pan; Chia-Wen Li; Ruey-Chih Su; Chiu-Ping Cheng; Choun-Sea Lin; Ming-Tsair Chan (Planta, 2010)

Influence of 14-day hind limb unloading on isolated muscle spindle activity in rats - Xue Hong Zhao; Xiao Li Fan; Xin Ai Song; Su Di Wu; Jun Chan Ren; Ming Xia Chen (Journal of Muscle Research and Cell Motility, 2010)

The CAG repeat in SCA12 functions as a cis element to up-regulate PPP2R2B expression - Chih-Hsin Lin; Chiung-Mei Chen; Yi-Ting Hou; Yih-Ru Wu; Hsiu-Mei Hsieh-Li; Ming-Tsan Su; Guey-Jen Lee-Chen (Human Genetics, 2010)

All-trans retinoic acid promotes smooth muscle cell differentiation of rabbit bone marrow-derived mesenchymal stem cells - Zhong-yuan Su; Ying Li; Xiao-li Zhao; Ming Zhang (Journal of Zhejiang University-SCIENCE B, 2010)

The phylogeny analysis of MyoG gene in different pig breeds - Li Zhu; Xue-Wei Li; Su-Rong Shuai; Ming-Zhou Li; Lei Chen; Yi-Ren Gu; Kai Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2010)

A tomato bZIP transcription factor, SlAREB, is involved in water deficit and salt stress response - Tsai-Hung Hsieh; Chia-Wen Li; Ruey-Chih Su; Chiu-Ping Cheng; Sanjaya; Yi-Chien Tsai; Ming-Tsair Chan (Planta, 2010)

The interaction between interferon-induced protein with tetratricopeptide repeats-1 and eukaryotic elongation factor-1A - Hong-Tao Li; Yong-Ping Su; Tian-Min Cheng; Jian-Ming Xu; Jie Liao; Ji-Chuan Chen; Chang-You Ji; Guo-Ping Ai; Jun-Ping Wang (Molecular and Cellular Biochemistry, 2010)

RA induces the neural-like cells generated from epigenetic modified NIH/3T3 cells - Xi-Mei Zhang; Qiu-Ming Li; Dong-Ju Su; Ning Wang; Zhi-Yan Shan; Lian-Hong Jin; Lei Lei (Molecular Biology Reports, 2010)

Responses of two rice cultivars differing in seedling-stage nitrogen use efficiency to growth under low-nitrogen conditions - Wei Ming Shi; Wei Feng Xu; Su Mei Li; Xue Qiang Zhao; Gang Qiang Dong (Plant and Soil, 2010)

Changes in H2O2 content and antioxidant enzyme gene expression during the somatic embryogenesis of Larix leptolepis - Shou-gong Zhang; Su-ying Han; Wen-hua Yang; Hua-li Wei; Ming Zhang; Li-wang Qi (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Increased serum interleukin 17 in patients with systemic lupus erythematosus - Xue-Fei Zhao; Hai-Feng Pan; Hui Yuan; Wen-Hui Zhang; Xiang-Pei Li; Gui-Hong Wang; Guo-Cui Wu; Hong Su; Fa-Ming Pan; Wen-Xian Li; Lian-Hong Li; Guo-Ping Chen; et al. (Molecular Biology Reports, 2010)

An improved process for cell disruption and astaxanthin extraction from Phaffia rhodozyma - An-Feng Xiao; Hui Ni; Hui-Nong Cai; Li-Jun Li; Wen-Jin Su; Qiu-Ming Yang (World Journal of Microbiology and Biotechnology, 2009)

Prevalence of human metapneumovirus in hospitalized children with respiratory tract infections in Tianjin, China - Xiao-yan Li; Jin-ying Chen; Mei Kong; Xu Su; Yan-ping Yi; Ming Zou; Hua Zhang (Archives of Virology, 2009)

Drepanocladus longifolius (Amblystegiaceae), an addition to the moss flora of King George Island, South Shetland Islands, with a review of Antarctic benthic mosses - Su-Ping Li; Ryszard Ochyra; Peng-Cheng Wu; Rodney D. Seppelt; Ming-Hong Cai; Hai-Ying Wang; Cheng-Sen Li (Polar Biology, 2009)

Des-γ-carboxy prothrombin stimulates human vascular endothelial cell growth and migration - Su-Bo Wang; Yan-Na Cheng; Shu-Xiang Cui; Julia Li Zhong; S. G. Ward; Li-Rui Sun; Ming-Hui Chen; Norihiro Kokudo; Wei Tang; Xian-Jun Qu (Clinical & Experimental Metastasis, 2009)

Sequences and genesis of the Yellow River terraces from Sanmen Gorge to Kouma - Huai Su; Junping Wang; Baotian Pan; Qingzhong Ming; Qiong Li (Journal of Geographical Sciences, 2009)

Environmental estrogenic effects and gonadal development in wild goldfish (Carassius auratus) - Chun-Ri Li; Sang-Hoon Lee; So-Sun Kim; Andre Kim; Keun Woo Lee; Ming Lu; Hee-Eun Kim; Im-Jung Kwak; Yun-Ju Lee; Dong-Kyoo Kim; Jung-Sick Lee; Shin-Won Kang; et al. (Environmental Monitoring and Assessment, 2009)

A population-based, case–control study of green tea consumption and leukemia risk in southwestern Taiwan - Yau-Chang Kuo; Chu-Ling Yu; Chen-Yu Liu; Su-Fen Wang; Pi-Chen Pan; Ming-Tsang Wu; Chi-Kung Ho; Yu-Shing Lo; Yi Li; David C. Christiani (Cancer Causes & Control, 2009)

Expression and localization of Tmie in adult rat cochlea - Mao-Chang Su; Jiann-Jou Yang; Ming-Yung Chou; Chung-Han Hsin; Ching-Chyuan Su; Shuan-Yow Li (Histochemistry and Cell Biology, 2008)

Characterization of tomato zonate spot virus, a new tospovirus in China - Jia-Hong Dong; Xiao-Fei Cheng; Yue-Yan Yin; Qi Fang; Ming Ding; Ting-Ting Li; Li-Zhen Zhang; Xiao-Xia Su; Jenifer Huang McBeath; Zhong-Kai Zhang (Archives of Virology, 2008)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Identification and expression analysis of hepcidin-like cDNAs from pigeon (Columba livia) - Yu Ming Fu; Su Ping Li; Yue Feng Wu; Yan Zhong Chang (Molecular and Cellular Biochemistry, 2007)

Observation of amyloid precursor protein cleavage and Aβ generation in living cells by using multiphoton laser scanning microscopy - Xiao-Qing Li; Su-Ming Zhang; Hua-Jing Yang; Zhi-Hong Zhang (Neuroscience Bulletin, 2007)

Effects of rosiglitazone on native low-density-lipoprotein-induced respiratory burst in circulating monocytes and on the leukocyte–endothelial interaction in cholesterol-fed rats - Long Sheng Lu; Li Man Hung; Chang Hui Liao; Chau Chung Wu; Ming Jai Su (Naunyn-Schmiedeberg's Archives of Pharmacology, 2007)

Rice Allelopathy Induced by Methyl Jasmonate and Methyl Salicylate - Hai Hong Bi; Ren Sen Zeng; Li Ming Su; Min An; Shi Ming Luo (Journal of Chemical Ecology, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Mapping QTLs for Phosphorus-Deficiency Tolerance at Wheat Seedling Stage - Junying Su; Yanmei Xiao; Ming Li; Quanyou Liu; Bin Li; Yiping Tong; Jizeng Jia; Zhensheng Li (Plant and Soil, 2006)

Cloning and Characterization of OsORC2, A New Member of Rice Origin Recognition Complex - Ke-Gui Li; Jin-Shui Yang; Kotb Attia; Wei Su; Guang-Ming He; Xiao-Yin Qian (Biotechnology Letters, 2005)

Production of biologically active GM-CSF in sugarcane: a secure biofactory - Ming-Li Wang; Cindy Goldstein; Winston Su; Paul H. Moore; Henrik H. Albert (Transgenic Research, 2005)

Refolding of a recombinant full-length non-structural (NS3) protein from hepatitis C virus by chromatographic procedures - Ming Li; Anton Poliakov; U. Helena Danielson; Zhiguo Su; Jan-Christer Janson (Biotechnology Letters, 2003)

Stability of tumor necrosis factor-α during ion exchange chromatography - Ming Li; Yunshan Wang; Weijun Li; Zhiguo Su (Biotechnology Letters, 2003)

Refolding of superoxide dismutase by ion-exchange chromatography - Ming Li; Zhi-Guo Su (Biotechnology Letters, 2002)

Multiple genotypes of mitochondrial DNA within a horse population from a small region in Yunnan province of China - Wen Wang; Ai-hua Liu; Shi-ying Lin; Hong Lan; Bing Su; De-wen Xie; Li-ming Shi (Biochemical Genetics, 1994)

Genetic diversity in the Chinese pangolin (Manis pentadactyla) inferred from protein electrophoresis - Bing Su; Rui-Qing Liu; Ying-xiang Wang; Li-ming Shi (Biochemical Genetics, 1994)

Multiple genotypes of mitochondrial DNA within a horse population from a small region in Yunnan province of China - Wen Wang; Ai-hua Liu; Shi-ying Lin; Hong Lan; Bing Su; De-wen Xie; Li-ming Shi (Biochemical Genetics, 1994)

Genetic diversity in the Chinese pangolin (Manis pentadactyla) inferred from protein electrophoresis - Bing Su; Rui-Qing Liu; Ying-xiang Wang; Li-ming Shi (Biochemical Genetics, 1994)